Preparation and quality detection method of modified cementitious material based on carbide slag and phosphogypsum
Patent Information
- Application Number
- CN202610878098.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]第一点,由于高温水热生成的半水石膏稳定温度阈值在40℃以上,水洗除杂过程易造成活性硫酸钙损耗、氟离子嵌入石膏晶格缺陷位,使得材料适配性与低温服役环境热力学条件相悖,进而使得超薄构件低温下石膏逆向水化膨胀开裂、超细注浆粉料内嵌氟盐长期缓释结晶堵塞导流孔隙,这也使得常规工艺无法同步实现活性保留与低温耐盐蚀的问题
[0096]1、本发明以电石渣、磷石膏、矿渣多种工业固废为核心原料,通过阶梯温控除水、低温转晶与晶格原位固结预处理工艺,有效消除固废原料含水率不均、晶相不稳定、杂质易析出的缺陷;搭配复合盐类组分分步激发协同仿生溶液微观改性技术,充分激活固废潜在胶凝活性,大幅提升工业固废的资源化利用率,实现固废无害化、高值化再生利用,节能环保且生产成本低廉。
Smart Images

Figure CN123003238A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic cementitious materials prepared from industrial solid waste and their testing technology, particularly to methods for preparing and testing quality of modified cementitious materials based on carbide slag and phosphogypsum. Background Technology
[0002] The large-scale disposal of carbide slag and phosphogypsum has become a key research area for the building materials industry. At present, most mass-produced cementitious products on the market are based on conventional roadbed and masonry mortar, which usually cannot meet the material requirements of special projects with component thickness ≤3mm, low temperature and high fluoride corrosion, and design service life of more than 15 years. The gap in customized technology for specific scenarios (such as ultra-thin walls of soil-covered rainwater collection cellars, micro capillary trenches in phosphate fertilizer plants, thin anti-seepage layers for high-sulfur tailings ponds, photovoltaic bases in desert and saline-alkali areas, etc.) is gradually becoming apparent.
[0003] Currently, in the industry, raw material modification generally involves high-temperature hydrothermal preparation of hemihydrate gypsum, followed by washing with clean water to remove soluble phosphorus and fluoride impurities. Then, in the production process, a one-time powder mixing, overall addition of activator, and standard constant temperature and humidity curing are adopted. The quality control of the finished product is achieved through average testing based on national standards, such as macroscopic mechanical analysis, single-step ion leaching, and infrared full-spectrum qualitative analysis.
[0004] However, when existing mature technologies are applied to ultra-thin seepage-proof components and special seepage-proof structures with ultra-long service cycles, the following obvious technical problems exist:
[0005] Firstly, since the stable temperature threshold of hemihydrate gypsum generated by high-temperature hydrothermal treatment is above 40℃, the water washing and impurity removal process easily causes the loss of active calcium sulfate and the embedding of fluoride ions into the defect sites of gypsum crystal lattice. This makes the material compatibility contradictory to the thermodynamic conditions of the low-temperature service environment, which in turn causes the gypsum to reverse hydration expansion and cracking at low temperatures in ultra-thin components, and the long-term slow-release crystallization of fluoride salts embedded in ultra-fine grouting powder to block the flow pores. This also makes it impossible for conventional processes to simultaneously achieve the problems of activity retention and low-temperature salt corrosion resistance.
[0006] Secondly, because national standard testing is often based on the average characterization logic of homogeneous cement, it cannot distinguish between the free phosphorus and fluorine states and the lattice-bound states, nor can it quantify the gel polymerization decay and the microscopic deterioration of the interface. As a result, although the product passes the acceptance test, it gradually causes the overall seepage prevention failure after actual service. Furthermore, general testing is even more unable to predict the risk of long-term hidden failure.
[0007] Based on this, the present invention designs a method for preparing and testing the quality of modified cementitious materials based on carbide slag and phosphogypsum, which is necessary for realizing efficient resource-based disposal of industrial solid waste and refined quality control of materials. Summary of the Invention
[0008] To solve one of the above-mentioned technical problems, the present invention adopts the following technical solution: a method for preparing and testing the quality of modified cementitious materials based on carbide slag and phosphogypsum, comprising the following steps: S1, performing a stepped temperature-controlled dehydration process on carbide slag and phosphogypsum, placing the dehydrated dry powder in an atmospheric pressure salt solution system to complete low-temperature gypsum crystallization treatment, simultaneously carrying out in-situ lattice consolidation, collecting liquid phase ion activity, crystal phase metastable persistence parameters, and multiple working condition characteristic parameters, including fluoride ion lattice distortion coefficient, relative water vapor partial pressure of the cover soil, trace organic matter crystal surface retardation coefficient, calcium ion supersaturation precipitation critical activity, and crystal phase metastable retention coefficient during the drying stage, constructing a raw material modification working condition dataset, and completing the pretreatment of solid waste raw materials.
[0009] S2. After the raw material pretreatment in S1 is completed, the pretreated carbide slag and phosphogypsum solid waste powders are mixed with the slag substrate in a whole-area dry powder homogenization process according to the ratio of calcium, silicon, sulfur and aluminum elements to obtain a uniform composite powder raw material.
[0010] After the S3 and S2 powders are mixed, the composite salt activating component is composed of one or more of sulfates, aluminates, alkali metal silicates, and carbonates. The composite salt activating component acts as an activator and awakening agent, and is a mixed additive that combines multiple environmentally friendly salt materials to make the powder react quickly, harden, and become stronger, thus making it a qualified cementitious material. S1 and S2 process the main raw materials: carbide slag, phosphogypsum, and slag substrate (solid waste powder main material system), and the composite salt activating component is used as an external functional auxiliary material.
[0011] The composite salt activating components were separated and the stepwise activation control was implemented. The layered feeding operation of pre-mixing dry powder phase and delayed addition of mixed water phase was completed in sequence to obtain a uniform and stable fresh gel slurry.
[0012] After the S4 and S3 pulping processes are completed, the fresh gel slurry is subjected to graded pressure molding and matching curing operations to prepare specimens. During the entire specimen molding and curing process, continuous in-situ monitoring of hydration conductivity is carried out, and early hydration ion evolution parameters are collected in real time.
[0013] S5. After the S4 specimen has been cured to the required standard, the cured specimen is cut into layers and multiple sets of parallel test samples are prepared in different areas.
[0014] After the S6 and S5 samples were prepared, multi-stage continuous fractional extraction was carried out on the parallel samples in the partitioned area to detect the diffusion and occurrence state of phosphorus and fluorine impurities in the gel matrix, and to quantitatively determine the diffusion hindrance characteristics of impurities in different occurrence forms in the matrix.
[0015] After the extraction and detection of impurities S7 and S6 were completed, the samples were subjected to quantitative analysis by infrared spectroscopy deconvolution and microscopic detection by single-point nanoindentation in different regions. The degree of polymerization of CSH gel and the microscopic mechanical characteristic parameters of the interface were collected simultaneously to complete the comprehensive calibration of the microstructure and mechanical properties of the samples.
[0016] S8. Based on the measured working condition parameters, impurity diffusion parameters, microstructure parameters and interface mechanical parameters collected throughout the process from S1 to S7, the overall quality test and comprehensive performance evaluation of the cementitious material are completed.
[0017] Among them, the quantitative analysis of infrared spectroscopy deconvolution involves splitting overlapping characteristic absorption peaks and using the area of the split characteristic peaks to quantitatively calculate the degree of CSH gel polymerization, which characterizes the degree of cross-linking polymerization density inside the gel.
[0018] By constructing a power-law calculation model for interface damage and a quantitative relationship between gel polymerization degree and long-term strength using multi-dimensional measured parameters, we can achieve quantitative analysis of interface degradation of modified cementitious materials under saline-alkali erosion environment and accurate prediction of ultra-long service performance of more than 15 years, thus completing refined quality testing and performance evaluation of the entire material preparation process.
[0019] To make the technical solution of the present invention clearer, the present invention will now be further described. When performing the S1 stepped temperature control dewatering process, the two types of solid waste raw materials, carbide slag and phosphogypsum, are first placed into the temperature control equipment respectively. The moisture removal is completed according to the three-stage time gradient of low temperature equilibrium, medium temperature dewatering and high temperature desorption. The temperature control parameters of each stage are adaptively matched according to the initial moisture content of the solid waste raw materials.
[0020] After the step-by-step dehydration is completed, the dried powder is immediately put into the atmospheric pressure salt solution system for low-temperature crystal transformation reaction. The entire process is carried out in an atmospheric pressure, low temperature and constant temperature environment to avoid the thermodynamic instability of gypsum crystal phase caused by high temperature.
[0021] After the crystallization process is completed, the wet planetary co-grinding operation is started to complete the in-situ consolidation of soluble phosphorus and fluorine impurities in the solid-liquid coupled grinding environment. Simultaneously, the fluoride ion lattice distortion coefficient, the relative water vapor partial pressure of the cover soil, the crystal plane retardation coefficient of trace organic matter, the critical activity of calcium ion supersaturation precipitation, and the metastable retention coefficient of the crystal phase during the drying stage are collected and entered into the raw material modification working condition dataset. This provides all the input parameters for the correction formula of the metastable existence time of hemihydrate gypsum, realizing the crystal phase stability calibration and dynamic correction.
[0022] This process uses a metastable survival time correction formula for hemihydrate gypsum to calibrate the crystal phase stability. This formula is used after the low-temperature brine soaking and crystal transformation step to calculate the stability of the newly formed hemihydrate gypsum crystals, specifically: how long they can be stably preserved, how easily they deteriorate, and to calibrate the stability period of the crystals produced in the crystal transformation process. The specific metastable survival time correction formula for hemihydrate gypsum is as follows:
[0023] .
[0024] In the formula: The duration of the metastable state of the hemihydrate gypsum crystalline phase is expressed in hours (h) and ranges from 12,000 to 20,000 hours.
[0025] The effective duration of low-temperature crystal transformation under normal pressure is expressed in hours, with a range of 2 to 6 hours. The lattice distortion coefficient for fluoride ions ranges from 0.01 to 0.10. The critical activity for supersaturated precipitation of calcium ions is dimensionless and ranges from 1.05 to 1.20, determined according to the standard for determination of ion activity in aqueous solution GB / T30492-2013. The relative water vapor partial pressure under soil cover conditions is taken as 0.60 to 0.90. The value is the crystal plane retardation coefficient of trace organic matter, ranging from 0.85 to 0.98; The value is the metastable retention coefficient of the crystal phase during the drying stage, ranging from 0.90 to 0.99.
[0026] It should be explained that existing technologies generally use a linear superposition model to describe the influence of impurities on crystal phase stability, completely ignoring the nonlinear thermal activation effect of lattice distortion, resulting in a prediction error exceeding 30%. This invention quantifies the synergistic effect of fluoride ion lattice distortion and calcium ion supersaturation activity through an exponential term, accurately reflecting the nonlinear variation law of phase transition activation energy. Regarding parameter determination, the fluoride ion lattice distortion coefficient is calculated according to the formula in GB / T26140-2010 after determining the lattice constant using X-ray diffraction. The calcium ion supersaturation activity is determined using the ion-selective electrode method according to GB / T30492-2013. All other parameters are obtained using the general methods specified in the corresponding national standards. The parameter adjustment strategy is as follows: when the fluorine content of the raw material is higher than 0.5%, Take the upper limit of 0.10, and at the same time... Extended to 6 hours; when the soil cover thickness is greater than 50cm, Take the upper limit of 0.90. Take the lower limit of 0.85.
[0027] Taking a green mine comprehensive construction project of a lead-zinc mine as an example, this project includes three sub-projects: emergency grouting in the mine area, dry stacking and seepage prevention of tailings dam, and agricultural rainwater collection cellars for ecological restoration in the surrounding area. This formula is applied to the raw material pretreatment process of the cementitious material for the lining of the 2.5mm ultra-thin rainwater collection cellar in the ecological restoration sub-project.
[0028] The rainwater harvesting cellar is covered with 40cm of soil. The local soil contains 2.8% humus, and the groundwater contains 0.35mg / L of fluoride. Tests have shown that... , , , , ,set up .
[0029] Substituting into the formula, we get: The estimated service life of the project is 22,224 hours, which falls within the reasonable range of 12,000-20,000 hours. This fully meets the service requirements for the region's eight-month rainy season (March to October) each year, and provides a safety margin of more than 1.6 times. However, if the existing linear model is used for calculation, the predicted result is only 1.02 years, with an error of 40.2%, which cannot guarantee the safety of the project.
[0030] To make the technical solution of the present invention clearer, the present invention will now be further described. After the completion of the S1 raw material pretreatment process, the S2 dry powder homogenization and mixing process will be performed.
[0031] First, based on the industry standard for mineral phase balance of solid waste gelling hydration, the molar ratio range of the four core elements calcium, silicon, sulfur and aluminum in the system was determined, and the mixing mass ratio of pretreated carbide slag, phosphogypsum powder and S95 slag substrate was strictly limited.
[0032] Then all dry powder components are put into the mixing equipment. First, a low-speed premixing method is used to achieve the initial dispersion of large component materials, and then the high-speed fine mixing mode is switched to eliminate local component segregation and agglomeration.
[0033] Segmented mixing sequence operation can ensure the microscopic mixing uniformity of various powders, providing a homogeneous material basis for subsequent step-by-step activation, hydration reaction, and crystal phase stabilization, thus avoiding problems such as differences in hydration rate and local structural defects caused by material inhomogeneity from the source.
[0034] To make the technical solution of the present invention clearer, the present invention will now be further described. After the S2 dry powder homogenization and mixing operation is completed, the S3 step-by-step activation and control process is performed.
[0035] First, the compound salt is separated into two groups of materials: a dry powder solid phase and an aqueous solution phase, and the mass separation ratio range of the two groups of materials is fixed.
[0036] In the final stage of dry powder mixing, a solid phase activating component is added to ensure that the solid phase activator is uniformly attached to the surface of the solid waste powder.
[0037] After the dry powder mixing system has become homogeneous and stable, the pre-dissolved liquid phase activation component is then uniformly added into the mixing system.
[0038] By using differentiated addition methods before and after addition, the alkalinity and sulfate ion release rate of the system can be controlled stepwise. This avoids the defects of instantaneous violent hydration reaction and local salting-out enrichment caused by traditional one-time full addition. It is suitable for the hydration stability requirements of ultrafine grouting powder and ultrathin lining components.
[0039] To make the technical solution of the present invention clearer, the present invention will now be further described. In the process of performing the S4 molding and curing and in-situ monitoring process, the fresh cementitious slurry is first subjected to graded pressure molding in the order of low pressure venting, medium pressure shaping and high pressure compaction. The molding pressure and holding time of each stage are limited to parameter ranges that are suitable for seepage prevention conditions.
[0040] After molding, a constant temperature curing system or a dry-wet alternating curing system is matched according to the service scenario.
[0041] During the early hydration window of slurry molding and curing, continuous in-situ monitoring of hydration conductivity was initiated throughout the process. Simultaneously, the surrounding rock geothermal drift correction coefficient, electrode passivation film growth rate, capillary water ion precipitation coefficient, and mineral dust ion adsorption coefficient were collected to perform multi-dimensional dynamic correction of the monitoring baseline and eliminate the influence of multiple interferences from the underground confined environment on the detection data.
[0042] In the process of multi-dimensional dynamic correction of the monitoring baseline, the logarithmic correction formula for multiple interference factors of hydration conductivity is used to complete the data correction:
[0043] .
[0044] In the formula:
[0045] : Environmentally corrected hydration conductivity, dimensionless conductivity, unit S / m, range of 0.05~0.50S / m;
[0046] The original conductivity values collected in situ on-site are in the form of conductivity and the unit is S / m.
[0047] : Correction factor for geothermal drift of surrounding rock, dimensionless (reciprocal of time), unit s⁻¹, range 1.0 × 10⁻¹ -6 ~5.0×10 -6 s -1 It is determined in accordance with the Thermal Testing Specification for Enclosed Spaces in Mines MT / T1064-2007;
[0048] : Effective duration of early hydration monitoring, in the dimension of time, in seconds, with a range of 1080–1920 seconds;
[0049] Electrode passivation film growth rate coefficient, dimensionless (reciprocal of time), unit s⁻¹, range 1.0 × 10⁻¹. -4 ~5.0×10 -4 s⁻¹, calibrated according to the electrochemical sensor calibration specification JJF1527-2015;
[0050] Electrode passivation characteristic time constant, dimensionless in time, unit in seconds, with a value of 3600 s, determined according to the general rules of electrochemical measurement methods GB / T20245.1-2006;
[0051] Capillary bleeding ion precipitation coefficient, dimensionless, with a value range of 0.01 to 0.05, determined according to the method for determining the bleeding rate of cement paste GB / T1346-2011;
[0052] : Ion adsorption coefficient of mine dust, dimensionless, with a value range of 0.005 to 0.02, calibrated according to the Mine Dust Detection Standard MT / T793-2006.
[0053] The logarithmic correction formula for hydration conductivity multi-interference factors is used to dynamically correct the monitoring baseline and correct the measured conductivity data affected by multiple factors during in-situ monitoring.
[0054] It should be explained that the design concept of this formula is based on the electrochemical interference superposition theory and Tafel's logarithmic law. It is customized in multiple dimensions for the extreme monitoring environment of emergency grouting in mines. The core difference from the existing technology is that the existing technology only uses simple linear drift correction, completely ignoring the nonlinear growth characteristics of electrode passivation, and the distortion rate of monitoring data often exceeds 40%. This invention quantifies the logarithmic growth law of the electrode passivation film by logarithmic terms and integrates the correction coefficients of three independent interferences in a product form, which is more in line with the actual interference superposition mechanism.
[0055] The surrounding rock geothermal drift correction coefficient is used to compensate for inaccurate temperature measurements caused by excessively high underground geothermal activity. The calculation involves collecting surrounding rock temperature data hourly for 24 consecutive hours to determine the average surrounding rock temperature and diurnal temperature variation, based on the calculation formula in the technical specifications for narrow-gauge overhead line mining locomotives. Calculation; where C is the geothermal drift correction factor for the surrounding rock. The diurnal temperature difference of the surrounding rock over a 24-hour period. This is the average temperature of the surrounding rock over 24 hours; this coefficient is used to correct for data offsets caused by environmental geothermal activity when detecting hydration temperature.
[0056] The electrode passivation film growth rate coefficient was obtained by experimental measurement using an electrochemical workstation according to the electrochemical testing methods specified in the electrochemical workstation metrological calibration standard. These are general constants specified in the national standard for basic electrochemical measurements, and no additional determination is required.
[0057] The parameter adjustment strategy is as follows: when the mine depth is greater than 400m, Take the upper limit of 5.0 × 10 -6 s -1When the underground dust concentration is greater than 10 mg / m³ 3 hour, Take the upper limit of 0.02; when the water-cement ratio of the slurry is greater than 0.6, Take the upper limit of 0.05.
[0058] Taking the above-mentioned comprehensive green mine construction project of a lead-zinc mine in Huanjiang County, Hechi City, Guangxi as an example, this formula is applied to the process quality control procedure of emergency grouting material for 0.2μm micro-cracks in the 320m middle section of the mining area production sub-project.
[0059] The grouting project requires an effective pumping time of 25 minutes, a downhole temperature of 27.5℃, and a dust concentration of 7.5 mg / m³. 3 The water-cement ratio of the slurry is 0.55.
[0060] On-site measured original conductivity After measurement , , , ,set up .
[0061] Substituting into the formula, we get: Geothermal correction term Electrode passivation correction item Water seepage and mineral dust correction items ,final It is within a reasonable range of 0.05 to 0.50 S / m.
[0062] To make the technical solution of the present invention clearer, the present invention will now be further described. After the S4 specimen molding and curing process is completed and meets the standards, the S5 specimen preparation process is carried out:
[0063] Layered cutting is completed using a non-disturbance precision cutting process along the uniform thickness direction of the molded specimen;
[0064] After cutting, multiple sets of parallel standard samples were prepared, and they were classified and sealed according to the testing requirements of impurity detection, microstructure detection, and interface mechanical detection.
[0065] All samples are stored in a constant temperature and humidity sealed environment to ensure the accuracy and parallelism of data from subsequent multi-dimensional testing experiments, and to provide qualified sample carriers for subsequent fractional extraction and microscopic characterization processes.
[0066] To make the technical solution of the present invention clearer, the present invention will now be further described. After the preparation of the S5 partitioned sample is completed, the S6 multi-stage continuous graded extraction process is carried out: the three-stage time-series extraction system of weak acid dissolution, medium salt dissolution and strong complexation is used in sequence to peel off the free leakage state, surface complexation state and lattice solidification state of the gel matrix step by step.
[0067] The dissociation constants of the buffer solutions and the equilibrium pH of the extraction systems at all levels strictly adhere to the environmental protection testing standards for solid waste.
[0068] The entire extraction process is carried out at a constant temperature and allowed to stand still. The surface complexation equilibrium coefficient of phosphorus and fluoride ions is collected in real time to accurately define the diffusion hindrance characteristics of impurities in different forms.
[0069] When collecting the surface complexation equilibrium coefficient of phosphorus and fluoride ions, real-time measurement is completed by the cooperation of two machines: an electrochemical workstation and an online phosphorus and fluoride ion detector. The growth rate coefficient of the electrode passivation film is tested by the electrochemical workstation, and the metrological performance of the instrument is verified in accordance with the current general calibration requirements for electrochemical analysis instruments.
[0070] Specifically, when using a multi-channel online ion analyzer in conjunction with an electrochemical workstation to collect data, the online ion analyzer is equipped with phosphorus and fluoride ion selective electrodes to continuously collect the concentration of free phosphorus and fluoride ions in the liquid phase in real time; the electrochemical workstation, relying on a three-electrode testing system, measures the complexation equilibrium coefficient of phosphorus and fluoride ions on the surface of the cementitious substrate in situ; and based on the two sets of measured parameters, the diffusion hindrance ability of adsorbed and free impurities is quantified.
[0071] The following needs to be explained in detail: Phosphorus and fluoride ion detector (with a dedicated probe): The probe is immersed in the slurry water to measure the amount of free phosphorus and fluoride impurities in the water at all times, transmitting a set of data per second; Electrochemical workstation: Connected to the material electrode, it measures in real time the tightness of phosphorus and fluoride adhering to the material surface (that is, the surface complexation equilibrium coefficient); Data aggregation of the two machines: The machine automatically compares the impurities adhering to the material and the impurities floating in the water, distinguishing which impurities are easy to move around and which are firmly stuck and cannot move, and calculating the rate at which each impurity is blocked from spreading.
[0072] This time-series graded extraction mode breaks through the detection limitations of traditional single-step full-volume leaching, and can accurately distinguish between leakable harmful components and inert solidified components under hazardous waste conditions, thus achieving refined environmental graded quality control of buffer building materials.
[0073] To make the technical solution of the present invention clearer, the present invention will now be further described. After the S6 impurity extraction and detection step is completed, the S7 infrared spectroscopy quantitative analysis step is performed:
[0074] Before detection, the CSH oligomer characteristic peak splitting threshold was pre-calibrated according to the silicate gel spectroscopy quantitative standard, which served as the criterion for splitting spectral data.
[0075] Subsequently, infrared spectroscopy was performed on the sample, and the half-width at half-maximum (FWHM) shift of the silicon-oxygen tetrahedron characteristic peak and the baseline drift of the hydroxyl peak were collected simultaneously. The detection error caused by dust and impurity peaks and capillary scattering loss was filtered out by a preset threshold.
[0076] The above scheme quantifies the degree of gel decalcification and polymerization attenuation caused by long-term salt and alkali corrosion based on the effective characteristic peak data after splitting, and realizes the long-term deterioration prediction of special cementitious materials for ultra-long service photovoltaic bases.
[0077] To make the technical solution of this invention clearer, the invention will now be further described. After the infrared spectroscopy analysis process is completed, the micron-level contact transition zone between the gelation and tailings of the sample is subjected to zoned single-point nanoindentation detection:
[0078] During the testing process, the following parameters were simultaneously collected: the interface sulfur segregation softening coefficient, the local alkali dissolution modulus attenuation coefficient, the stress concentration coefficient at the tip of ettringite needle crystals, the unloading rebound deformation coefficient of the pore region, and the polished surface damage thickness correction coefficient. A damage accumulation model for the interface transition zone was constructed, and the degree of material damage accumulated slowly was calculated through the model.
[0079] Specifically, due to the long-term erosion of materials by sunlight, water, and salt and alkali, internal fine cracks, pores, and crystal damage will gradually accumulate and grow larger. This solution uses a damage accumulation model of the interface transition zone to predict the extent of cumulative damage at the interface location, and can predict in advance when cracking and failure will occur, thus predicting a long-term service life of 15 years.
[0080] The calculation formula for the damage accumulation model in the interface transition zone is as follows:
[0081] ;
[0082] In the formula: The equivalent degradation modulus of the seepage prevention interface is expressed in terms of stress, with units of GPa and a range of 5–15 GPa.
[0083] The intrinsic micro-elastic modulus of the cementitious matrix is measured in units of stress and GPa, with a range of 10–20 GPa. The elastic modulus and hardness of the material are determined by nanoindentation method.
[0084] The interfacial sulfur segregation softening coefficient is dimensionless and ranges from 0.05 to 0.20, determined according to the material surface element distribution analysis specifications.
[0085] The value is the alkali-dissolution modulus attenuation coefficient in the micro-region, dimensionless, ranging from 0.10 to 0.30, and is calibrated according to the alkali-aggregate reaction test method for cement-based materials.
[0086] is the stress concentration factor at the tip of ettringite needle crystals, dimensionless, ranging from 1.2 to 1.8, determined according to the standard for stress concentration analysis in solid mechanics;
[0087] The unloading rebound deformation coefficient of the porous region is dimensionless, ranging from 0.03 to 0.10, and is calibrated according to the nanoindentation test method.
[0088] The value is a dimensionless correction factor for the thickness of the polished surface damage, ranging from 0.95 to 0.99, and is calibrated according to the material microscopic sample preparation specifications.
[0089] It should be explained that this model is designed in depth for the interface failure mechanism of the dry-piled anti-seepage cushion layer of high-sulfur tailings. The core difference between this model and the existing technology is that the existing technology generally adopts a linear damage model, ignores the cumulative amplification effect of damage, and has a large error in the prediction of interface failure. This invention, by quantifying the synergistic damage effect of sulfur segregation and alkali corrosion, and introducing surface damage correction for sample preparation, can better reflect the nonlinear evolution law of interface damage.
[0090] Regarding parameter determination, the interfacial sulfur segregation softening coefficient was determined by electron probe microanalysis, the local alkali corrosion modulus attenuation coefficient was determined by accelerated alkali corrosion test, and the 1.5 power exponent, a common power law exponent for interfacial damage of cement-based materials, was determined based on industry experience.
[0091] The parameter adjustment strategy is as follows: when the sulfur content of the tailings is greater than 15%, Take the upper limit of 0.20; when the alkali content of the cementitious material is greater than 0.8%, Take the upper limit of 0.30; when the sample polishing accuracy is less than 0.5μm, Take the lower limit of 0.95.
[0092] Taking the aforementioned comprehensive green mine construction project of a lead-zinc mine in Huanjiang County, Hechi City, Guangxi Province as an example, this formula is applied to the finished product acceptance and testing process of the single-layer anti-seepage cushion layer for dry stacking of high-sulfur lead-zinc tailings in the tailings dam sub-project.
[0093] The subbase is designed for a 15-year service life, with a tailings sulfur content of 12%, a cementitious material alkali content of 0.6%, and an ettringite aspect ratio of 15 in the interface transition zone. Measurements show that... , , , , , .
[0094] Substituting into the formula, we obtain the synergistic damage term of sulfur segregation and alkali corrosion. Stress concentration and porosity springback coupled damage terms ,final This value is within a reasonable range of 5 to 15 GPa, which meets the accuracy requirements for evaluating the long-term service performance of high-sulfur tailings seepage prevention cushions.
[0095] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0096] 1. This invention uses various industrial solid wastes such as carbide slag, phosphogypsum, and slag as core raw materials. Through step-temperature controlled dehydration, low-temperature crystal transformation, and in-situ lattice consolidation pretreatment processes, it effectively eliminates defects such as uneven moisture content, unstable crystal phase, and easy precipitation of impurities in solid waste raw materials. Combined with the stepwise activation and synergistic biomimetic solution micro-modification technology of composite salt components, it fully activates the potential gelling activity of solid waste, significantly improves the resource utilization rate of industrial solid waste, realizes the harmless and high-value recycling of solid waste, and is energy-saving, environmentally friendly, and has low production costs.
[0097] 2. This invention innovatively adopts a stepwise sequential addition process of composite salt activating components into the solid and liquid phases, combined with the microscopic interface regulation effect of biomimetic modified solutions. This allows for precise control of the early hydration reaction rate of the cementitious system, avoiding defects such as excessively rapid hydration, matrix cracking, and loose structure caused by traditional single-addition of activators. It effectively optimizes the degree of CSH gel polymerization, refines the pore structure of the matrix, improves defects in the transition zone of the cementitious-aggregate interface, and significantly enhances the overall density, mechanical strength, and structural stability of the modified cementitious material.
[0098] 3. This invention effectively fixes free, complexed, and lattice-state phosphorus and fluorine impurities in the cementitious matrix by combining multi-level continuous graded extraction and impurity detection with in-situ lattice consolidation. At the same time, relying on the interface optimization effect of biomimetic solutions, it further inhibits the diffusion and migration of impurities inside the matrix, significantly reduces the risk of leaching of harmful ions in industrial solid waste, solves the technical pain points of easy leakage of impurities and poor environmental stability of traditional solid waste-based cementitious materials, and significantly improves the environmental safety of the material during service.
[0099] 4. This invention is equipped with a complete testing process including in-situ hydration monitoring, quantitative analysis by infrared spectroscopy, and nano-indentation micromechanical testing. This allows for the accurate acquisition of raw material operating parameters, hydration evolution parameters, microstructure parameters, and interface damage parameters. By establishing a power-law model for cumulative interface damage and a gel polymerization degree-strength correlation mechanism, it achieves a comprehensive quantitative evaluation from raw material pretreatment and preparation to microscopic properties and long-term service performance. This overcomes the limitations of traditional cementitious materials that rely solely on macroscopic properties to determine quality, effectively improving product quality stability and engineering adaptability. Attached Figure Description
[0100] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. In all the drawings, similar elements or components are generally identified by similar reference numerals.
[0101] Figure 1 This is a flowchart of the method of the present invention. Detailed Implementation
[0102] The embodiments of the technical solution of the present invention will now be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore merely examples and should not be used to limit the scope of protection of the present invention. The specific method of the present invention is as follows: Figure 1 As shown in the image.
[0103] Example 1: To make the technical solution of the present invention clearer, the present invention will now be further described. The present invention provides a method for preparing and testing the quality of modified cementitious materials based on carbide slag and phosphogypsum. The steps are as follows: S1. First, a stepped temperature-controlled dehydration process is performed on the carbide slag and phosphogypsum. The raw materials are spread into a layer with a thickness of no more than 5 cm. The material is first equilibrated at a low temperature of 40-50℃ for 2-3 hours, then heated to a medium temperature of 60-70℃ for 4-6 hours for dehydration, and finally heated to a high temperature of 80-90℃ for 1-2 hours for desorption. Then, a sodium chloride atmospheric pressure salt solution system with a mass concentration of 5%-8% is placed in the solution, and the low temperature gypsum crystallization treatment is completed at a constant temperature of 45-55℃. At the same time, wet planetary co-grinding lattice in-situ consolidation is carried out, controlling the solid content of the slurry to be 60%-70%, the grinding speed to be 300-400 rpm, and the grinding time to be 2-3 hours. Liquid phase ion activity and crystal phase metastable survival parameters are collected to construct a raw material modification working condition dataset.
[0104] S2. Then, based on the ratio of calcium, silicon, sulfur and aluminum elements, the pretreated solid waste powder and S95 slag substrate are mixed in a homogeneous dry powder mixture throughout the entire process, controlling the calcium-silicon molar ratio to be 1.2-1.8 and the sulfur-aluminum molar ratio to be 0.8-1.2.
[0105] S3. Subsequently, the composite salt is split and step-by-step activation control is performed. First, 40%-60% of the activator is added during the dry powder mixing stage, and the remaining 40%-60% is pre-dissolved in the mixing water and then added at a uniform and delayed rate of 5-10 liters / minute to obtain fresh slurry.
[0106] S4. Simultaneous grading and pressure molding of fresh slurry and matching curing operations. Grading and pressure molding: The mixed fresh cementitious slurry is poured into the interior of a standard steel molding mold. First, it is degassed under low pressure of 0.2-0.5MPa for 2-3 minutes, then shaped under medium pressure of 1.0-1.5MPa for 3-5 minutes, and finally compacted under high pressure of 2.0-2.5MPa for 5-10 minutes. Curing is carried out at a constant temperature of 20±2℃ or alternating dry and wet curing (24 hours dry / 24 hours wet). Continuous in-situ monitoring of hydration conductivity is carried out throughout the process. Platinum electrodes are inserted into the slurry to a depth of 2-3 cm, and data is collected every 10 seconds to collect early hydration ion evolution parameters in real time, providing original data support for subsequent specimen performance testing and degradation analysis.
[0107] S5. After the specimen has been cured for 28 days, use a diamond cutter to cut it evenly in layers along the thickness direction of the specimen. The cutting speed is 5-10 mm / min and the cooling water flow rate is 1-2 liters / min. Prepare no less than 6 sets of parallel test specimens in each zone. The size of each set of specimens is 40mm×40mm×10mm.
[0108] S6. Further multi-stage continuous fractional extraction was performed on the partitioned samples. Three-stage extraction was carried out using 0.1 mol / L acetic acid solution, 1 mol / L magnesium chloride solution, and 0.05 mol / L EDTA solution. The solid-liquid ratio of each extraction stage was 1:10, the extraction time was 2 hours, and the extraction temperature was 25±1℃. The diffusion and occurrence parameters of phosphorus and fluorine impurities in various forms inside the gel matrix were monitored.
[0109] S7. Finally, the sample was subjected to sequential infrared spectral deconvolution quantitative analysis and regional single-point nanoindentation microscopic detection, with an infrared scanning range of 4000-4000 cm⁻¹. -1 4cm resolution -1 The number of scans was 32; the maximum load of nanoindentation was 100mN, the loading time was 10 seconds, the holding time was 5 seconds, and the unloading time was 10 seconds; the degree of gel polymerization and the micromechanical characteristics of the interface were collected to complete the comprehensive performance calibration of the sample.
[0110] S8. By constructing a power-law calculation model for interface damage and a quantitative relationship between gel polymerization degree and long-term strength through multi-dimensional measured parameters, we can realize the quantitative analysis of interface degradation of modified cementitious materials under saline-alkali erosion environment and the accurate prediction of ultra-long service performance of more than 15 years, and complete the refined quality inspection and performance evaluation of the entire material preparation process.
[0111] Comprehensive performance calibration of a sample refers to the process of obtaining data on the internal structure and stress-resistance of the material through testing, and finally comprehensively judging the quality and performance of the sample. The specific judgment steps are as follows:
[0112] The first step involves sequentially testing and collecting data. First, an infrared instrument is used to scan the sample, eliminating interference errors generated during testing and measuring relevant data on the quality of the material's internal structure. Then, a nanometer-based testing instrument is used to test the stress on the sample's contact surfaces, measuring relevant data on the material's strength and durability, thus collecting all necessary test data.
[0113] The second step is to determine the acceptance criteria. In accordance with industry-standard requirements, the acceptable range for material structure and load-bearing performance should be clearly defined, and clear and unified criteria for judging quality should be established. Material quality should not be judged based on a single data point to ensure fair and accurate results.
[0114] The third step is to compare and verify all the data. The structural and stress data measured above, along with the previously measured environmental and safety data, are compared and cross-checked to avoid errors from a single test and to comprehensively and accurately determine the overall quality of the sample.
[0115] The specific verification method is as follows: Three different types of test data are compared one-to-one with the qualification standards to verify each other and identify any omissions or deficiencies. The first type verifies environmental safety data to check whether harmful impurities in the material meet standards and to determine if the material is safe and pollution-free. The second type verifies infrared structural data to check whether the internal structure of the material is dense, robust, and resistant to aging. The third type verifies nanomechanical data to test whether the material's contact surfaces are firm, durable, and resistant to cracking and damage. Conclusions are not drawn solely from any single data point. If one data point is weak, the other two data points can be used to verify the true performance, offsetting any accidental errors from a single test, and providing a comprehensive, accurate, and reliable assessment of the overall quality of the sample.
[0116] The fourth step is to finally determine the material's performance level. Based on the verification results of all data, a comprehensive assessment is made of the safety, structural integrity, and durability of the sample, identifying the suitable construction application scenarios for the material, and completing the final determination of the overall material performance.
[0117] It should be noted that this technical solution can dispose of industrial solid waste. Each ton of cementitious material can dispose of 0.35 tons of carbide slag and 0.3 tons of phosphogypsum, reducing carbon emissions by more than 60% compared to ordinary cement. It also reduces production costs, with raw material costs only 40% of those of ordinary silicate cement. Furthermore, the preparation process is simple, requiring no high-temperature calcination, and its energy consumption is far lower than that of cement production.
[0118] Furthermore, this technical solution can be adapted to the construction of 2-3mm ultra-thin linings, and the grout fluidity can reach more than 180mm without bleeding or segregation; in addition, it can meet the grouting requirements of 0.15-0.3μm micro-cracks, and the powder fineness all passes through a 325-mesh sieve, which can penetrate into micro-cracks that conventional grouting materials cannot reach.
[0119] In terms of service life, it can achieve a predicted long-term service life of over 15 years. The stepped temperature control dehydration scheme avoids abrupt changes in the gypsum crystal phase through gradient heating, preserving the activity of hemihydrate gypsum; wet planetary co-milling utilizes grinding mechanical energy to promote the insertion of fluoride ions into the gypsum lattice, achieving in-situ consolidation of impurities; stepwise excitation uses phase-separated doping of activators to moderate the hydration rate and suppress local salting out; multi-stage continuous graded extraction accurately distinguishes the occurrence forms of impurities, meeting environmental acceptance requirements; the combined use of infrared spectroscopy and nanoindentation can evaluate the long-term degradation risk of the material from both microstructure and mechanical property dimensions.
[0120] To make the technical solution of this invention clearer, the invention will now be further described. In the S1 stepped temperature-controlled dehydration process, the two types of solid waste raw materials, carbide slag and phosphogypsum, are first crushed to a particle size of less than 2 mm, and coarse particles larger than 2 mm are screened out. Then, they are placed in a forced-air drying oven, and moisture removal is completed according to a three-stage time gradient: low-temperature equilibrium, medium-temperature dehydration, and high-temperature desorption. The temperature control parameters for each stage are adaptively matched according to the initial moisture content of the raw materials: when the initial moisture content is greater than 30%, the medium-temperature dehydration time is extended to 6-8 hours; when the initial moisture content is less than 20%, the medium-temperature dehydration time is shortened to 3-4 hours. After the stepped dehydration is completed, the dried powder is immediately added to a stainless steel reactor containing a sodium chloride solution, and the stirrer is turned on at 100-150 rpm. Stirring is performed at a constant speed, maintaining a constant temperature environment of 45-55℃ under normal pressure throughout the process, with a reaction time of 2-6 hours to avoid thermodynamic instability of the gypsum crystal phase caused by high temperature. After the crystallization process is completed, the slurry is transferred to a planetary ball mill, and zirconium oxide grinding balls with diameters of 10mm, 20mm, and 30mm are added at a ball-to-material mass ratio of 3:1. Wet planetary co-milling is then started to complete the in-situ consolidation of soluble phosphorus and fluorine impurities in a solid-liquid coupled grinding environment. Simultaneously, the fluoride ion lattice distortion coefficient, the relative water vapor partial pressure of the cover soil, the crystal plane retardation coefficient of trace organic matter, the critical activity of calcium ion supersaturation precipitation, and the metastable retention coefficient of the crystal phase during the drying stage are collected and entered into the raw material modification condition dataset. All parameters can be commissioned to a local testing institution with CMA qualification to measure them according to the corresponding national standards.
[0121] This process uses a metastable duration correction formula for hemihydrate gypsum to complete the crystal phase stability calibration:
[0122] In the formula: The duration of the metastable state of the hemihydrate gypsum crystalline phase is measured in hours (h), with a range of 12,000 to 20,000 hours. It fully covers the service life of agricultural rainwater harvesting cellars in karst areas for two consecutive rainy seasons, with a safety margin of more than 30%, and is determined in accordance with the requirements of the technical specifications for rural water supply engineering regarding the design service life of small rainwater harvesting facilities. The effective duration of low-temperature crystal transformation under normal pressure is measured in hours (2-6 hours). The fluoride ion lattice distortion coefficient is dimensionless, ranging from 0.01 to 0.10, and is calibrated according to the inorganic crystal microstructure testing standard. The critical activity for supersaturated precipitation of calcium ions is dimensionless and ranges from 1.05 to 1.20, determined according to the standard for determination of ion activity in aqueous solutions. The relative water vapor partial pressure under the soil cover condition is dimensionless and ranges from 0.60 to 0.90, determined according to the soil hydrological observation specifications. The value is the crystal plane retardation coefficient of trace organic matter, dimensionless, ranging from 0.85 to 0.98, calibrated according to the specifications for colloid and surface chemical analysis; The metastable retention coefficient of the crystal phase during the drying stage is dimensionless and ranges from 0.90 to 0.99. It is calibrated according to the gypsum crystal phase transformation detection method.
[0123] It should be noted that the purpose of this technical solution is to solve the industry problem of reverse hydration expansion and cracking of hemihydrate gypsum in ultra-thin cellar wall lining in karst areas. This technical solution can improve the crystalline phase stability of hemihydrate gypsum and extend the service life of cementitious materials; achieve in-situ solidification of soluble phosphorus and fluorine impurities, and ensure that the leaching toxicity meets the requirements of hazardous waste identification standards; and the atmospheric pressure low-temperature crystallization process is safe and reliable, requires no high-pressure equipment, and has low investment costs.
[0124] It should also be explained that this technical solution quantifies the inhibitory effect of soil trace organic matter on the gypsum crystal phase; at the same time, it establishes a quantitative relationship between crystal phase stability and process parameters, which can dynamically adjust the crystallization time according to the groundwater fluoride content and soil moisture in different regions.
[0125] Specifically, in the technical solution, the reverse hydration of hemihydrate gypsum to dihydrate gypsum is a thermally activated process. Fluoride ion embedding into the gypsum lattice leads to lattice distortion, increasing the phase transition activation energy. This change in activation energy has an exponential, rather than a nonlinear, effect on the phase transition rate. In the formula, the fluoride ion lattice distortion coefficient reflects the degree of damage to the crystal structure caused by impurities; the relative water vapor partial pressure of the cover soil determines the driving force of reverse hydration; the trace organic matter crystal plane retardation coefficient quantifies the molecular blocking effect of humic substances; the calcium ion supersaturation precipitation critical activity controls the nucleation rate of dihydrate gypsum; and the metastable retention coefficient of the crystal phase during the drying stage corrects the influence of subsequent processes on the crystal transformation effect.
[0126] The formula requires a detailed explanation, including the physical meaning, value range, measurement method, and standard basis of all characters in the formula, as follows: The duration of the metastable state of the hemihydrate gypsum crystalline phase is measured in hours (h), with a range of 12,000-20,000 hours. This range corresponds to 1.37-2.28 years, fully covering the service life of agricultural rainwater harvesting cellars in karst areas for two consecutive rainy seasons, with a safety margin of over 30%. It is determined based on the requirements for the design service life of small rainwater harvesting facilities in the technical specifications for rural water supply engineering.
[0127] The effective duration of low-temperature crystallization at normal pressure is measured in hours (h) and ranges from 2 to 6 hours. According to the regulations on the crystallization process of hemihydrate gypsum in gypsum building materials, when the crystallization time is less than 2 hours, the conversion rate of dihydrate gypsum to hemihydrate gypsum is less than 85%, which cannot meet the requirements for gelling activity. When the time is greater than 6 hours, hemihydrate gypsum will undergo secondary crystallization and growth, resulting in powder fineness exceeding 10% residue on a 325-mesh sieve, which is not suitable for ultra-thin lining construction.
[0128] The fluoride ion lattice distortion coefficient is dimensionless, ranging from 0.01 to 0.10, and is calculated according to the X-ray diffraction lattice constant determination method specified in the inorganic crystal microstructure testing standard. The calculation formula is as follows: ,in The lattice constant of fluorine-doped gypsum is... The standard lattice constant of pure dihydrate gypsum is 0.5679 nm, and the fluorine doping content in phosphogypsum of 0.1% to 1.0% corresponds exactly to this coefficient range.
[0129] The value is the critical activity for supersaturated precipitation of calcium ions, dimensionless, ranging from 1.05 to 1.20. It is determined according to the calcium ion selective electrode method in the standard for determination of aqueous solution ion activity. When the supersaturated activity is less than 1.05, calcium ions cannot precipitate effectively, and the crystallization reaction rate is too slow. When it is greater than 1.20, homogeneous nucleation will occur, producing a large amount of amorphous calcium phosphate precipitate, which affects the strength of cementitious materials.
[0130] The relative water vapor partial pressure under soil cover conditions is dimensionless and ranges from 0.60 to 0.90. Based on the soil water vapor partial pressure observation method in the soil hydrology observation specification, it corresponds to the annual average water vapor partial pressure range of 30-50cm soil cover thickness in the karst region of southwestern my country. When the soil cover thickness is less than 30cm, it is taken as 0.60, and when it is greater than 50cm, it is taken as 0.90.
[0131] The trace organic matter crystal surface retardation coefficient is dimensionless and ranges from 0.85 to 0.98. According to the surface adsorption coefficient determination method in the standard of colloid and surface chemical analysis, the value is equal to 1 minus the adsorption coverage of organic matter on the gypsum crystal surface, corresponding to the adsorption range of 1% to 5% of soil humus content.
[0132] The value is the metastable retention coefficient of the crystal phase during the drying stage. It is dimensionless and ranges from 0.90 to 0.99. Based on the thermal stability determination method of the gypsum crystal phase transformation detection method, it corresponds to the crystal phase retention rate of hemihydrate gypsum under low temperature drying conditions of 60-80℃. The value is 0.99 when the drying temperature is below 60℃ and 0.90 when the drying temperature is above 80℃.
[0133] Taking the 2.5mm ultra-thin rainwater collection cellar of an ecological restoration sub-project of a green mine project in Huanjiang County, Hechi City, Guangxi Province as an example, the fluorine content of phosphogypsum is 0.35%, corresponding to... The soil humus content is 2.8%, corresponding to an adsorption coverage rate of 9%, therefore... The soil cover thickness is 40cm, corresponding to The measured calcium ion activity value was 1.13, i.e. Drying temperature 70℃, corresponding to Set crystal transformation time .
[0134] Substitute into the formula and calculate step by step:
[0135] First, calculate the exponent. Then calculate the product of each correction factor. Finally obtained The year, or 19490h, falls within the reasonable range of 12000 to 20000h.
[0136] If the crystal transformation time is shortened to 2 hours, then The year, or 11143 hours, is slightly below the lower limit, requiring the crystal transformation time to be extended to over 2.2 hours; if the crystal transformation time is extended to 6 hours, then... The annual time limit is 33,430 hours, which exceeds the upper limit. The crystal transformation time can be appropriately shortened to 4 hours to reduce energy consumption.
[0137] To make the technical solution of this invention clearer, the invention will now be further described. After the completion of the S1 raw material pretreatment process, the S2 dry powder homogenization and mixing process is performed. First, according to the industry standard for solid waste gelling and hydration mineral phase balance, the molar ratio range of the four core elements (calcium, silicon, sulfur, and aluminum) within the system is determined, and the mass ratio of pretreated carbide slag is strictly limited to 30%-40%, phosphogypsum to 25%-35%, and S95 slag substrate to 25%-35%. Then, all dry powder components are put into a double-helix conical mixer, initially using a 30... Premix at a low speed of 50 rpm for 5-10 minutes to achieve initial dispersion of large components; then switch to high-speed fine mixing at 150-200 rpm for 15-20 minutes to eliminate local component segregation and agglomeration; after mixing, sieve using a 200-mesh standard sieve, the residue should not exceed 5%, if it does, remix for 5 minutes; this segmented mixing sequence can ensure the microscopic uniformity of the mixing of various powders, providing a homogeneous material basis for subsequent step-by-step activation, hydration reaction, and crystal phase stabilization, avoiding problems such as differences in hydration rate and local structural defects caused by material inhomogeneity from the source.
[0138] It should be noted that this technical solution addresses the problem of large performance fluctuations in cementitious materials caused by uneven composition of solid waste powder. It can ensure the balance of calcium, silicon, sulfur, and aluminum elements, and generate sufficient amounts of hydrated calcium silicate and ettringite, etc. It improves the uniformity of powder mixing, making the standard deviation of strength of the same batch of products less than 1.5 MPa. At the same time, it optimizes particle size distribution, improves slurry density, and reduces porosity.
[0139] In addition, this technical solution achieves customized adjustment of cementitious material performance through precise quality ratio control. For example, increasing the proportion of calcium carbide slag can increase early strength, while increasing the proportion of slag can improve later corrosion resistance. The segmented process of low-speed premixing and high-speed fine mixing avoids the loss of light component materials and eliminates the agglomeration of ultrafine powders. Furthermore, this solution introduces a 200-mesh sieve residue control index to ensure that the powder fineness meets the requirements of ultra-thin lining and micro-crack grouting.
[0140] This solution is based on the diffusion and shearing mechanisms of powder mixing: the low-speed premixing stage mainly relies on gravity diffusion to initially mix large particles evenly; the high-speed fine mixing stage mainly relies on mechanical shearing to break up powder agglomerates and achieve uniform dispersion at the microscale.
[0141] The conical structure of the double-helix conical mixer allows the material to circulate up and down during the mixing process, avoiding uneven mixing caused by material accumulation at the bottom.
[0142] When designing parameters, low-speed premixing at 30-50 rpm can prevent lightweight materials such as carbide slag from being carried away by the airflow, while high-speed fine mixing at 150-200 rpm can achieve a mixing uniformity of over 95% within 20 minutes. The residue on a 200-mesh sieve of no more than 5% ensures that all powder passes through the filter screen of the grouting pump without clogging.
[0143] For example, when the mass ratio of carbide slag is 35%, phosphogypsum is 30%, and slag is 35%, the compressive strength of the cementitious material after 28 days can reach 32.5 MPa, and the flexural strength can reach 6.5 MPa, which fully meets the requirements of cementitious materials for building structures.
[0144] Example 2: Based on Example 1, in order to make the technical solution of the present invention clearer, the present invention will now be further described. After the S2 dry powder homogenization and mixing operation is completed, the S3 step-by-step activation and control process is immediately executed.
[0145] The composite salt is divided into two groups of materials: a dry powder solid phase and an aqueous solution phase. The composite salt activator is composed of sodium sulfate and sodium carbonate in a mass ratio of 3:1. The mass ratio of the two groups of materials is 1:1. The solid phase activator is added in the final stage of dry powder mixing (i.e., the last 5 minutes of high-speed fine mixing) so that the solid phase activator is uniformly attached to the surface of the solid waste powder.
[0146] After the dry powder mixing system is homogeneous and stable, the pre-dissolved liquid phase activation component is uniformly added to the mixing system at a rate of 5-10 liters / minute using a metering pump, and the mixing time is controlled at 3-5 minutes.
[0147] By using a differentiated addition method before and after the addition, the alkalinity and sulfate ion release rate of the system are controlled step by step, avoiding the defects of instantaneous violent hydration reaction and local salt precipitation caused by traditional one-time full addition, and adapting to the hydration stability requirements of ultrafine grouting powder and ultrathin lining components.
[0148] The solid-phase activating component is a solid powder material composed of sodium sulfate and sodium carbonate in a mass ratio of 3:1, dissolved without water. The liquid-phase activating component is a salt solution formed by dissolving equal proportions of salts in water, which is added at a uniform wet rate using a metering pump after mixing.
[0149] The mixing system refers to the overall mixture of carbide slag and phosphogypsum main powders after homogenization and blending with S2 dry powder. The initial dry mixing yields a solid base material, which constitutes the matrix of the mixing system; after the subsequent addition of liquid phase activating components, all materials coexisting in solid and liquid phases are still collectively referred to as the mixing system.
[0150] It should be noted that this technical solution can solve the problems of excessively rapid hydration rate and localized salting-out expansion caused by the one-time full addition of traditional activators. Specifically, by controlling the setting time of the cementitious material, the initial setting time is controlled at 60-90 minutes, and the final setting time is controlled at 180-240 minutes; at the same time, the amount of hydration products generated is increased, and the degree of hydration can reach more than 75% after 28 days; it can also inhibit the excessive growth of ettringite and avoid poor volume stability.
[0151] This solution is well adapted to the construction of 2-3mm ultra-thin linings, reduces the peak hydration heat release rate by 40%, and avoids cracking of ultra-thin layers due to temperature stress; it meets the grouting requirements for 0.2μm micro-cracks, and extends the pumping time of the grout to 25-30 minutes, ensuring sufficient operation time for grouting.
[0152] Based on the ion diffusion mechanism of cementitious material hydration, the solid phase activator is first incorporated into the dry powder system and uniformly adheres to the surface of solid waste particles. It slowly dissolves in the early stage of mixing, providing initial alkalinity and initiating the hydration reaction. The liquid phase activator is then incorporated into the mixing system, releasing sulfate ions at a uniform rate to promote the continuous formation of ettringite.
[0153] This stepwise addition method keeps the alkalinity and sulfate ion concentration of the system within a reasonable range, avoiding the problems of excessively high local alkalinity and overly vigorous hydration reaction caused by one-time addition.
[0154] After optimization of the process parameters, the 3:1 compound ratio of sodium sulfate to sodium carbonate can balance the early strength and the later strength, the 1:1 split ratio can make the hydration rate curve the flattest, and the addition rate of 5-10 liters / minute can ensure that the liquid phase activator is uniformly dispersed in the slurry.
[0155] For example, the grouting material prepared using this process was used in a grouting project for 0.2μm micro-cracks in a 320m section of a lead-zinc mine in Hechi, Guangxi. The grouting pressure was stable at 0.8-1.2MPa, the compressive strength reached 5MPa after 24 hours and 15MPa after 7 days, and the water-blocking effect reached over 98%.
[0156] To make the technical solution of the present invention clearer, the present invention will now be further described. In the process of performing the S4 molding curing and in-situ monitoring process, fresh gelatinous slurry is first poured into a steel mold, the surface is scraped smooth and then placed on a pressure testing machine.
[0157] The gradation and pressurization molding process is completed in the following sequence: low-pressure venting, medium-pressure setting, and high-pressure compaction. First, apply a low pressure of 0.2-0.5 MPa and hold it for 2-3 minutes to expel air bubbles from the slurry. Then, apply a medium pressure of 1.0-1.5 MPa and hold it for 3-5 minutes to allow the slurry to initially set. Finally, apply a high pressure of 2.0-2.5 MPa and hold it for 5-10 minutes to fully compact the slurry.
[0158] After molding, the material is demolded and the curing system is matched according to the service scenario: for rainwater collection cellar lining and tailings dam seepage prevention, constant temperature curing at 20±2℃ and relative humidity above 95% is adopted; for underground emergency grouting, underground natural environment curing is adopted.
[0159] During the early hydration window period of slurry molding and curing (i.e., 18-32 minutes after mixing), continuous in-situ monitoring of hydration conductivity was carried out throughout the process. Two platinum electrodes were inserted into the slurry at a depth of 2-3 cm with a spacing of 5 cm between the electrodes, and conductivity data was collected every 10 seconds.
[0160] Simultaneously collect the surrounding rock geothermal drift correction coefficient, electrode passivation film growth rate, capillary water secretion ion precipitation coefficient, and mineral dust ion adsorption coefficient to perform multi-dimensional dynamic correction of the monitoring baseline and eliminate the influence of multiple interferences in the underground confined environment on the detection data.
[0161] In the process of multi-dimensional dynamic correction of the monitoring baseline, the logarithmic correction formula for multiple interference factors of hydration conductivity is used to complete the data correction:
[0162]
[0163] In the formula: The hydrated conductivity after environmental correction is measured in terms of conductivity, with units of S / m, and a range of 0.05 to 0.50 S / m.
[0164] The values are the raw conductivity values collected in situ on-site, with the dimension being conductivity and the unit being S / m;
[0165] This is the correction factor for geothermal drift in the surrounding rock, with dimensions of the reciprocal of time and units of seconds. -1 The value range is (1.0 × 10). -6 ~5.0×10 -6 )s -1 The values are based on the specifications or industry requirements for temperature drift correction in underground confined spaces. In addition, the reference range for the long-term geothermal drift rate of the surrounding rock in the confined mine is calculated by the coefficient through continuous 24-hour temperature measurement by the sensor.
[0166] The effective duration for early water hydration monitoring is measured in time, with the unit being seconds, and the value range is 1080–1920 s.
[0167] This is the electrode passivation film growth rate coefficient, with dimensions of the reciprocal of time and units of seconds (s). -1 The value range is (1.0 × 10). -4 ~5.0×10 -4 )s -1 Calibrate according to the electrochemical sensor calibration specification;
[0168] The characteristic time constant for electrode passivation is time in units of seconds, and is set to 3600 s. It is determined according to the general rules of electrochemical measurement methods.
[0169] The capillary bleeding ion precipitation coefficient is dimensionless and ranges from 0.01 to 0.05, determined according to the method for measuring the bleeding rate of cement paste.
[0170] The adsorption coefficient of ions in the mine dust is dimensionless and ranges from 0.005 to 0.02, calibrated according to the mine dust detection standard.
[0171] It should be noted that the purpose of this technical solution is to solve the problem of inaccurate monitoring of early hydration activity of emergency grouting materials in wells. The design of the solution can ensure the molding quality of cementitious specimens, with a 28-day compressive strength variation coefficient of less than 3%; real-time monitoring of the early hydration process of the grout, prediction of setting time and strength development; and matching the curing system according to different service scenarios to improve the performance stability of cementitious materials.
[0172] It should be noted that this scheme is the first to achieve multi-factor correction of conductivity monitoring data in complex downhole environments; it precisely locks the monitoring window period to 18-32 minutes after mixing, which corresponds exactly to the effective pumpable time of emergency grouting; it establishes a quantitative relationship between the corrected conductivity and the pumpability of the grout, and when the corrected conductivity is greater than 0.4 S / m, the grout will lose its fluidity and grouting must be stopped immediately.
[0173] It should be noted that, based on the theory of electrochemical ion migration, changes in ion concentration during the hydration process of cementitious materials will lead to changes in conductivity. By monitoring conductivity, the progress of the hydration reaction can be reflected in real time.
[0174] It should also be noted that geothermal drift of the surrounding rock will change the ion migration rate of the solution, electrode passivation will reduce the effective reaction area of the electrode, capillary efflux will change the ion concentration of the solution, and mineral dust adsorption will consume the ions in the solution.
[0175] The formula needs to be explained in detail. The hydration conductivity after environmental correction is measured in S / m, with dimensions of conductivity. The range is 0.05–0.50 S / m, corresponding to the typical conductivity range during the early hydration induction period of carbide slag-phosphogypsum-based cementitious materials. Based on the measurement data of cement paste conductivity in the cement hydration heat determination method, the conductivity of ordinary Portland cement during the induction period is 0.03–0.60 S / m. The activity of the cementitious material in this invention is slightly lower, so it is limited to 0.05–0.50 S / m. These are raw conductivity values collected in situ on-site, with the dimension of conductivity and the unit of S / m. They were measured in real-time using a DDS-11A platinum black electrode conductivity meter, with an electrode constant of 1.0 cm⁻¹. -1 ; This is the correction factor for geothermal drift in the surrounding rock, with dimensions of the reciprocal of time and units of seconds. -1 The value range is (1.0 × 10). -6 -5.0×10 -6 )s -1 According to the method for determining the rate of change of surrounding rock temperature in the thermal testing specifications for confined spaces in mines, the calculation formula is as follows: ,in This represents the change in surrounding rock temperature over 24 hours. The initial temperature corresponds to a daily temperature variation rate of 0.086–0.43℃ / d for the surrounding rock in lead-zinc mines at depths of 200–500m. The effective duration of early hydration monitoring is measured in time, with the unit being seconds. The value range is 1080–1920 seconds, corresponding to 18–32 minutes. According to the provisions of the technical specifications for underground grouting engineering in coal mines regarding the pumpable duration of emergency grouting materials, grouting operations cannot be completed if the pumpable duration is less than 18 minutes, and early strength development is too slow if it is greater than 32 minutes. This is the electrode passivation film growth rate coefficient, with dimensions of the reciprocal of time and units of seconds (s). -1 The specific range of values is (1.0 × 10). -4 ~5.0×10 -4 )s -1 According to the electrode passivation rate determination method in the electrochemical sensor calibration specification, the passivation rate of the platinum electrode in the corresponding alkaline environment was calculated by measuring the AC impedance spectrum of the electrode using an electrochemical workstation, which corresponds to 1 to 6 months of use. The characteristic time constant for electrode passivation is 3600 s, which is a time constant recognized by the electrochemical community both domestically and internationally, based on the general provisions for the characteristic time of metal electrode passivation in the general rules of electrochemical measurement methods. No additional measurement is required. The capillary bleeding ion precipitation coefficient is dimensionless and ranges from 0.01 to 0.05. Based on the bleeding rate determination method in the cement paste bleeding rate determination method, the value is equal to the paste bleeding rate, corresponding to the bleeding rate range of ultrafine grout with a water-cement ratio of 0.4 to 0.6. The adsorption coefficient of the mine dust is dimensionless, ranging from 0.005 to 0.02. It is calculated based on the dust adsorption capacity determination method in the mine dust detection specification, by measuring the adsorption capacity of the dust on a standard sodium chloride solution, corresponding to an underground dust concentration of 2–10 mg / m³. 3 The range of adsorption capacity.
[0176] Taking the grouting project for 0.2μm micro-fractures in a 320m section of a lead-zinc mine in Huanjiang County, Hechi City, Guangxi Province as an example, the mine depth is 320m, the surrounding rock temperature changes by 0.2℃ over 24 hours, the initial temperature is 27.5℃, and the actual measured value of η is 2.3×10. -6 s -1 Downhole dust concentration: 7.5 mg / m³ 3 ,correspond =0.011; water-cement ratio of slurry 0.55, bleeding rate 2.8%, corresponding to =0.028; Electrode usage time: 3 months, corresponding to =1.9×10 -4 s -1 Set monitoring duration =1500s; On-site measured original conductivity =0.21S / m.
[0177] Substituting into the formula and calculating step by step: We obtain It is approximately 0.201 S / m, which is within the reasonable range of 0.05-0.50 S / m.
[0178] To make the technical solution of the present invention clearer, the present invention will now be further described. After the S4 specimen molding and curing process is completed and meets the standards, the S5 specimen preparation process is carried out:
[0179] Layered cutting was performed using a diamond cutter along the uniform thickness direction of the molded specimen. Cooling water was turned on during cutting, with the flow rate controlled at 1-2 liters / minute and the cutting speed maintained at 5-10 mm / minute to avoid damage to the internal microstructure of the specimen caused by the high temperature generated during cutting. After cutting, no less than 6 sets of parallel standard samples were prepared, each with a size of 40 mm × 40 mm × 10 mm. The surface of the samples was wiped with anhydrous ethanol to remove cutting debris. According to the testing requirements of impurity detection, microstructure detection, and interface mechanical testing, the samples were divided into zones and classified, and placed into sealed bags and labeled with numbers. All samples were stored in a constant temperature and humidity sealed environment at 20 ± 2℃ and 50 ± 5% relative humidity for no more than 7 days to prevent premature aging, moisture absorption, and contamination of the samples, ensuring the accuracy and parallelism of the data from subsequent multi-dimensional testing, and providing a qualified sample carrier for subsequent fractional extraction and micro-characterization processes.
[0180] It should be noted that this technical solution prepares parallel samples of uniform size to ensure the repeatability and reproducibility of the test results; removes cutting debris from the sample surface to avoid impurities interfering with the test results; and stores the samples in separate sections to facilitate the orderly conduct of subsequent testing.
[0181] It should also be noted that a non-disturbance precision cutting process is adopted to control the damage to the microstructure of the sample to within 50μm during the cutting process; in addition, a constant temperature and humidity storage system is introduced to avoid aging phenomena such as carbonization and moisture absorption during the storage process; and by specifying a maximum storage time of 7 days, it is ensured that the test results can truly reflect the performance of the specimen after 28 days of curing.
[0182] This method is based on the temperature sensitivity of the material's microstructure. During diamond cutting, localized high temperatures are generated. When the temperature exceeds 100℃, the gypsum crystal phase undergoes a dehydration transformation, and the CSH gel decomposes, leading to distorted test results. Cooling water promptly removes the heat generated during cutting, controlling the temperature of the cutting area below 50℃. A cutting speed of 5-10 mm / min balances cutting efficiency and the degree of thermal damage. Wiping with anhydrous ethanol quickly removes surface debris without chemically reacting with the cementing material. Combined with a constant temperature and humidity environment, the moisture content of the sample remains stable, avoiding microstructural changes caused by moisture variations.
[0183] For example, when the cutting speed exceeds 10 mm / min, the temperature in the cutting area can reach over 150°C, which will cause hemihydrate gypsum to dehydrate and generate anhydrous gypsum, resulting in a crystal phase stability test result that is more than 30% higher; when the sample is stored for more than 7 days, the sample will carbonize, which will increase the intensity of the calcium carbonate characteristic peak in the infrared spectroscopy test result by more than 20%.
[0184] Example 3: Based on Example 2, to make the technical solution of the present invention clearer, the present invention will now be further described. After the preparation of the S5 partitioned sample is completed, the S6 multi-stage continuous fractional extraction process is carried out: the sample used for impurity detection is ground until it all passes through a 200-mesh standard sieve, and 1.000g of sample is accurately weighed and placed in a 50ml centrifuge tube; a three-stage sequential extraction system of weak acid dissolution, medium salt dissolution, and strong complexation is used in sequence: in the first stage, 20ml of 0.1mol / L acetic acid solution is added, the centrifuge tube is tightly capped, and it is placed on a shaker and shaken at 200 rpm for 2 hours, and then centrifuged at 4000 rpm for 10 minutes. The supernatant is taken to determine the free phosphorus and fluorine content; in the second stage, the centrifuge tube residue is added... Add 20 ml of 1 mol / L magnesium chloride solution to the centrifuge tube, repeat the above shaking and centrifugation steps, and take the supernatant to determine the content of complexed phosphorus and fluoride; in the third stage, add 20 ml of 0.05 mol / L EDTA solution to the residue in the centrifuge tube, repeat the above shaking and centrifugation steps again, and take the supernatant to determine the content of lattice-solidified phosphorus and fluoride; the entire extraction process of each stage is carried out in a constant temperature environment of 25±1℃, and after centrifugation, let it stand for 30 minutes before taking the supernatant; the surface complexation equilibrium coefficient of phosphorus and fluoride ions is collected in real time to accurately define the diffusion hindrance characteristics of impurities in different forms; this sequential graded extraction mode breaks through the detection limitations of traditional single-step full-volume leaching, and can accurately distinguish between leakable harmful components and inert solidified components under hazardous waste conditions, realizing refined environmental graded quality control of buffer building materials.
[0185] It should be noted that this technical solution simplifies the five-step extraction method into a three-stage extraction system suitable for cementitious materials for the first time, reducing the detection time from 72 hours to 8 hours and improving detection efficiency. By introducing the phosphorus and fluoride ion surface complexation equilibrium coefficient, the stability of complexed impurities is quantified, which solves the misconception in existing technologies that all complexed impurities are regarded as harmful components.
[0186] It should also be noted that this scheme is based on the solubility differences of impurities in different extractants in different forms: free phosphorus and fluorine impurities are easily soluble in weak acids and can be extracted by acetic acid solution; complexed phosphorus and fluorine impurities are tightly bound to the surface of colloidal particles and need to be replaced by high-concentration salt solution; lattice-fixed phosphorus and fluorine impurities are embedded in the crystal structure and need to be extracted by destroying the crystal structure with the strong complexing agent EDTA.
[0187] In the process parameter settings, 0.1 mol / L acetic acid solution can completely extract free impurities without damaging the colloidal structure; 1 mol / L magnesium chloride solution can effectively replace complexed impurities; and 0.05 mol / L LEDTA solution can dissolve phosphorus and fluorine impurities in the crystal lattice.
[0188] For example, when this method was used to detect the phosphorus and fluorine content of a certain cementitious material, the free phosphorus content was 0.02 mg / L, the complexed phosphorus content was 0.05 mg / L, the lattice-solidified phosphorus content was 1.2 mg / L, and the total phosphorus content was 1.27 mg / L, which meets the requirements of the integrated wastewater discharge standard. However, the total phosphorus content measured by the traditional single-step full-volume leaching method was 0.07 mg / L, which cannot distinguish between the permeable free phosphorus and the inert lattice-solidified phosphorus, leading to inaccurate environmental assessment results.
[0189] To make the technical solution of the present invention clearer, the present invention will now be further described. After the S6 impurity extraction and detection step is completed, the S7 infrared spectroscopy quantitative analysis step is performed:
[0190] Small pieces of material are ground into ultrafine powder, which can pass through a 300-mesh sieve. 1 mg of powder sample is mixed with 200 mg of dry potassium bromide powder and pressed into a transparent sheet with a diameter of 13 mm under a pressure of 10 MPa.
[0191] Before detection, the CSH oligomer characteristic peak splitting threshold was pre-calibrated to 0.05 according to the silicate gel spectroscopy quantitative standard, which served as the criterion for splitting spectral data and distinguishing between effective peaks and invalid impurity peaks.
[0192] The thin slice was then scanned using a Fourier transform infrared spectrometer with a scanning range of 4000-400 wavenumbers, a resolution of 4 wavenumbers, and 32 scans.
[0193] The half-width at half-maximum (FWHM) shift of the characteristic peaks of silicon-oxygen tetrahedra and the baseline drift of the hydroxyl peak are collected simultaneously. That is, the machine synchronously records the spectral changes of silicon-oxygen and hydroxyl groups inside the material. The baseline correction method is used to filter out the detection errors caused by dust and impurity peaks and scattering loss from capillary pores. That is, the erroneous data caused by dust and small pores are removed. The baseline points are selected at four points: 4000, 2000, 1000, and 400 to calibrate the baseline.
[0194] Based on the split effective characteristic peak data, the degree of gel decalcification and polymerization degree reduction caused by long-term salt and alkali corrosion is quantified, so as to realize the long-term deterioration prediction of special cementitious materials for ultra-long service photovoltaic bases. Specifically, using the processed effective data, the amount of calcium loss caused by long-term salt and alkali corrosion to loosen the internal skeleton of the material is calculated, and the number of years the photovoltaic base can be used is predicted and whether it will slowly deteriorate and be damaged.
[0195] Herein, 300-mesh sieve, 10 MPa tabletting, ratio of 1 mg: 200 mg, tablet diameter of 13 mm, and spectral parameters are all conventional processes for national standard silicate infrared testing; the threshold value of 0.05 is a general demarcation value for spectral quantification of C-S-H gel in the industry.
[0196] It should be noted that the purpose of this technical solution is to solve the problem that the traditional infrared spectroscopy method can only perform qualitative phase analysis and cannot quantitatively evaluate the degree of gel deterioration. In the technical solution, the polymerization degree of C-S-H gel is quantitatively determined by infrared spectral deconvolution technology. Specifically, the spectrum splitting (deconvolution) algorithm supporting the infrared instrument is used to separate the overlapping material absorption peaks, and the tightness of molecular aggregation inside the C-S-H gel (polymerization degree) is accurately calculated based on the size of the separated peaks, so as to judge how much the structure of the material deteriorates after being corroded by salt and alkali, solving the problem that the prior art cannot quantify the change of gel structure. By introducing the splitting threshold of the characteristic peak of C-S-H oligomer, the accuracy and repeatability of the deconvolution result are improved; in addition, by establishing the quantitative relationship between the gel polymerization degree and the long-term strength of the material, the service performance of the material for more than 15 years can be predicted.
[0197] Specifically for prediction, C-S-H gel is the internal skeleton of the material. The denser the skeleton molecules are entangled (the greater the polymerization degree P), the stronger the long-term compressive strength of the material. First, carry out aging tests on multiple groups of test blocks, measure the polymerization degree and the corresponding multi-year strength, calculate the fixed parameters to obtain the calculation formula; then only use infrared to measure the polymerization degree of the on-site sample, substitute it into the formula to calculate the strength after 15 years, and judge whether it can be used for a long time in photovoltaic bases and rainwater collection cellars; the specific formula adopts the following unary linear positive correlation model: , where is the long-term ultimate strength of the material (cured to a steady state, representing the long-term strength for 15 years and later, in MPa), is the polymerization degree of C-S-H gel measured by infrared deconvolution, is the strength reference constant (in MPa), is the correlation coefficient, B>0, the higher the polymerization degree, the higher the long-term strength; the specific step-by-step operation steps are as follows:
[0198] Step 1: Prepare multiple groups of parallel samples for accelerated aging: prepare dozens of cementitious test blocks according to the ratio of the present invention, and adopt a temperature-humidity accelerated aging test to simulate years of salt-alkali erosion in the natural environment.
[0199] Step 2: Detect the polymerization degree P of each group of samples by S7 infrared: sample each aged test block, grind and pass through a 300-mesh sieve, perform KBr tabletting, Fourier transform infrared scanning, and deconvolve and split the characteristic peaks, so as to measure the C-S-H polymerization degree P of the corresponding sample one by one.
[0200] Step 3: Measure the long-term strength through mechanical test : Perform a compressive test on the corresponding sample to obtain the measured long-term strength of each group .
[0201] Step 4: Data fitting to determine constants A and B: using multiple sets of ((P, Based on measured data, the least squares method was used to fit and solve for two constant values, A and B (measured values for this scheme: A=3.25, B=12.6), thus establishing the specific calculation formula for this material. =3.25+12.6P.
[0202] Step 5: Predict the service performance of the sample to be tested: Obtain the degree of polymerization P by actual production / on-site sampling and infrared testing, and substitute it into the above formula to calculate the long-term strength in 15 years; compare it with the strength required by the engineering design. If it meets the standard, it can meet the long-term service of more than 15 years. If it does not meet the standard, optimize the raw material ratio and activation process.
[0203] Example calculation: For instance, when the infrared detection value of the on-site sample is P=0.42: =3.25 + 12.6 × 0.42 = 8.542 MPa.
[0204] If the project requires a long-term strength of ≥7.0MPa, the strength of this material formula is sufficient to meet the service requirements of photovoltaic bases and karst rainwater collection cellars for more than 15 years.
[0205] The above scheme is based on molecular vibrational spectroscopy theory. Different chemical bonds have different vibrational frequencies, which will produce absorption peaks at specific positions in the infrared spectrum. The silicon-oxygen tetrahedral vibrational peak of CSH gel is located at 900-1200 cm⁻¹. -1 At this point, the peak is a broad peak formed by the superposition of vibrational peaks of silicon-oxygen tetrahedra with different degrees of polymerization. Using deconvolution technology, it can be separated into three sub-peaks: oligomer, mesomer, and polymer. The average degree of polymerization of the gel can be calculated based on the area ratio of the sub-peaks. The process parameters were optimized: 300-mesh grinding ensures uniform particle size of the sample and reduces infrared scattering; the ratio of 1 mg sample to 200 mg potassium bromide achieves suitable absorbance; 4 cm... -1 The high resolution and 32 scans balance detection accuracy and time.
[0206] For example, after a photovoltaic base cementitious material has been in service in a saline-alkali environment for 5 years, the average degree of polymerization of CSH gel has decreased from 2.8 to 1.9. Using this method, its strength retention rate can be accurately calculated to be 72%, with a deviation of only 3.5% from the on-site sampling and measurement results.
[0207] To make the technical solution of this invention clearer, the invention will now be further described. After the infrared spectroscopy analysis process is completed, the sample gel-tailings micron-level contact transition zone is then subjected to zoned single-point nanoindentation detection:
[0208] The sample used for interfacial mechanical testing was inlaid with epoxy resin, and then polished with 400 grit, 800 grit, 1200 grit and 2000 grit sandpaper in sequence, and then polished with diamond polishing agent until the surface roughness was less than 0.1 μm.
[0209] The interface between the cement and tailings was located under an optical microscope, and the transition zone region of 50 micrometers on both sides of the interface was marked.
[0210] Test points were taken every 10 micrometers in the transition zone area, and the indentation spacing was greater than 10 times the length of the indentation diagonal. The test was conducted using a nanoindenter with a maximum load of 100mN, a loading time of 10 seconds, a holding time of 5 seconds, and an unloading time of 10 seconds.
[0211] During the testing process, the following parameters were simultaneously collected: interfacial sulfur segregation softening coefficient, local alkali dissolution modulus attenuation coefficient, stress concentration coefficient at the tip of ettringite needle crystals, unloading rebound deformation coefficient in the pore region, and polished surface damage thickness correction coefficient. A damage accumulation model for the interfacial transition zone was constructed, and the degree of gradual material damage was calculated using this model. Based on the cumulative damage growth rate, it was determined when the material interface reached the critical damage threshold, thus determining the actual service life of the material. This process optimized the carbide slag-phosphogypsum cementitious formula and curing process to meet the long-term use requirements of photovoltaic bases and karst rainwater harvesting cellars.
[0212] The calculation formula for the damage accumulation model in the interface transition zone is as follows:
[0213] ;
[0214] In the formula: The equivalent degradation modulus of the seepage prevention interface is expressed in terms of stress, with units of GPa and a range of 5–15 GPa.
[0215] The intrinsic micro-elastic modulus of the cementitious matrix is measured in units of stress and GPa, with a range of 10–20 GPa. The elastic modulus and hardness of the material are determined by nanoindentation method.
[0216] The interfacial sulfur segregation softening coefficient is dimensionless and ranges from 0.05 to 0.20, determined according to the material surface element distribution analysis specifications.
[0217] The value is the alkali-dissolution modulus attenuation coefficient in the micro-region, dimensionless, ranging from 0.10 to 0.30, and is calibrated according to the alkali-aggregate reaction test method for cement-based materials.
[0218] is the stress concentration factor at the tip of ettringite needle crystals, dimensionless, ranging from 1.2 to 1.8, determined according to the standard for stress concentration analysis in solid mechanics;
[0219] The unloading rebound deformation coefficient of the porous region is dimensionless, ranging from 0.03 to 0.10, and is calibrated according to the nanoindentation test method.
[0220] The value is a dimensionless correction factor for the thickness of polished surface damage, ranging from 0.95 to 0.99, and is calibrated according to the material microscopic sample preparation specifications.
[0221] It should be noted that this technical solution can determine the micromechanical properties of the cementitious matrix and tailings particles; evaluate the bonding strength of the interfacial transition zone; and analyze the damage evolution law of the material.
[0222] This technical solution effectively realizes the detection of mechanical property distribution in the micron-level interface transition zone, with a spatial resolution of up to 1 μm. By establishing a power-law model of interface damage accumulation, the synergistic damage effect of sulfur segregation and alkali corrosion is quantified. Furthermore, by introducing a polishing surface damage correction coefficient, the influence of the sample preparation process on the detection results is eliminated.
[0223] Based on the contact mechanics theory of nanoindentation, the elastic modulus and hardness of the material can be calculated by measuring the load-displacement curves of the indenter during loading and unloading. The interfacial transition zone is a weak area between the cementitious material and tailings particles, typically 10-50 μm thick, with mechanical properties 30%-50% lower than the matrix, and is the origin of seepage prevention failure. Industry experience suggests that the introduction of the 1.5 power in the formula is due to the cumulative amplification effect of interfacial damage; sulfur segregation-induced interfacial softening accelerates the alkali corrosion process, and the synergistic effect of these two factors exhibits a non-linear relationship.
[0224] The formula requires a detailed explanation, including the physical meaning, value range, measurement method, and standard basis of all characters in the formula, as follows: The equivalent degradation modulus of the seepage prevention interface is measured in stress, with the unit being GPa and a value range of 5-15 GPa. This corresponds to the typical elastic modulus range of the transition zone between cement-based materials and high-sulfur tailings. According to the interface modulus measurement data in the test method of interface mechanical properties of cement-based composite materials, the interface modulus of ordinary cement and sand and gravel aggregate is 10-20 GPa. The interface modulus of the cementitious material and high-sulfur tailings in this invention is slightly lower due to sulfur segregation. The original micro-elastic modulus of the cementitious matrix is expressed in terms of stress and in GPa. The value range is 10–20 GPa. The elastic modulus is determined according to the nanoindentation method, which is a method for determining the elastic modulus and hardness of materials. The corresponding micro-modulus range of the carbide slag-phosphogypsum-based cementitious material at 28 days of age is given. When the slag content is greater than 30%, the upper limit is taken, and when it is less than 25%, the lower limit is taken. The interfacial sulfur segregation softening coefficient is dimensionless, ranging from 0.05 to 0.20, and is determined using the electron probe microanalysis method according to the material surface elemental distribution analysis specification. The calculation formula is as follows: ,in The interfacial sulfur content, This represents the sulfur content in the matrix, corresponding to a segregation degree of 5%-20% in the sulfur content of the tailings. The value is the alkali corrosion modulus attenuation coefficient in the micro-region, dimensionless, ranging from 0.10 to 0.30. It is determined by the accelerated alkali corrosion test method of the alkali-aggregate reaction test method for cement-based materials. It is the modulus attenuation rate of cementitious materials after soaking in 1 mol / L NaOH solution for 6 months, corresponding to cementitious materials with an alkali content of 0.4% to 0.8%. The stress concentration factor at the tip of ettringite needle crystals is dimensionless and ranges from 1.2 to 1.8. It is calculated according to the stress concentration factor calculation method for needle-shaped crystals in the standard for stress concentration analysis in solid mechanics. It corresponds to ettringite needle crystals with an aspect ratio of 10-20. The larger the aspect ratio, the higher the stress concentration factor. The unloading rebound deformation coefficient of the pore region is dimensionless and ranges from 0.03 to 0.10. It is determined by the rebound coefficient method of nanoindentation test and is equal to the ratio of unloading rebound displacement to maximum indentation displacement. It corresponds to cement-based materials with porosity of 10%-30%. The value is a dimensionless correction factor for the thickness of polished surface damage, ranging from 0.95 to 0.99. It is based on the polished surface damage correction method according to the material microscopic sample preparation specification, and corresponds to polished samples with a surface roughness of 0.05-0.5 μm. The larger the surface roughness, the smaller the correction factor.
[0225] It should also be noted that the 1.5 power exponent in the formula is an industry-experienced benchmark value for the cumulative calculation of interfacial damage in cementitious materials, adapted to the damage evolution law of the carbide slag-phosphogypsum-based composite cementitious system. This exponent can be adaptively fine-tuned by those skilled in the art based on fluctuations in raw material composition, differences in service environment, and engineering accuracy requirements, flexibly adapting to the damage quantification calculation requirements of different working conditions; its physical meaning is that interfacial damage has a nonlinear cumulative amplification effect, and the degree of damage increases to the power of 1.5 over time.
[0226] Taking a high-sulfur lead-zinc tailings dry-piled anti-seepage cushion layer project in Huanjiang County, Hechi City, Guangxi Province as an application example, the sulfur content of the tailings raw material in this project is 12%. Key parameters of the cementitious material interface and matrix were obtained through electron probe microanalysis, and each damage characteristic coefficient was determined one by one. Combined with the power-law formula for cumulative damage in the interface transition zone of this invention, the degradation modulus was quantitatively calculated. At the same time, the accuracy was compared with the traditional linear damage model. The specific parameter values and step-by-step calculation process are as follows:
[0227] I. Basic test parameter values:
[0228] 1. Sulfur segregation softening coefficient: The measured sulfur content at the interface of the cementitious material is 1.38%, and the sulfur content in the cementitious matrix is 1.2%. According to the formula for calculating the sulfur segregation coefficient, the following can be obtained: ;
[0229] 2. Local Alkali Dissolution Modulus Attenuation Coefficient: The initial alkali content of the cementitious material is 0.6%. After accelerated alkali corrosion aging test, the overall modulus of the material decreases by 20%, i.e. ;
[0230] 3. Stress concentration factor at the tip of ettringite needle crystals: Microscopic observation shows that the aspect ratio of ettringite crystals is 15, corresponding to the value... ;
[0231] 4. Unloading rebound deformation coefficient in the porous region: The measured porosity of the seepage prevention layer is 20%, and the corresponding value is... ;
[0232] 5. Polishing surface damage thickness correction coefficient: The microscopic surface roughness of the sample is 0.1 μm, and the corresponding value is... ;
[0233] 6. Initial elastic modulus of the cementitious matrix: .
[0234] In the damage formula of this invention, 1.5 is the industry experience benchmark value for the cumulative calculation of interface damage of cementitious materials. It can be adaptively fine-tuned according to the fluctuation of raw material composition, the difference of service environment and the requirements of engineering testing accuracy, so as to meet the damage quantification calculation requirements of different working conditions.
[0235] II. Step-by-step calculation of the power-law damage model of this invention:
[0236] The first step is to calculate the synergistic damage term of sulfur segregation and alkali corrosion:
[0237] .
[0238] The second step is to calculate the coupled damage terms of ettringite stress concentration, pore rebound, and surface damage:
[0239] .
[0240] The third step is to calculate the total damage retention coefficient of the interface transition zone:
[0241] .
[0242] Step 4: Calculate the elastic modulus of the interface after degradation.
[0243] .
[0244] The calculation results are within the reasonable engineering range of 5-15 GPa for the interfacial modulus of cementitious materials, and the data are valid.
[0245] III. Comparison of calculations with traditional linear damage models:
[0246] Using existing conventional linear damage models: Substitute parameters to calculate: .
[0247] IV. Accuracy Comparison Analysis: The true value of the interface degradation modulus of the seepage prevention layer measured on-site is 12.8 GPa. Deviation calculation is performed based on this value: Deviation calculated using the traditional linear model: ; Calculation bias of the power-law model in this invention: .
[0248] The comparison shows that the multi-factor power-law damage model of the present invention has significantly improved calculation accuracy. Compared with the traditional linear model, the error is greatly reduced and the calculation accuracy is improved. It can effectively meet the needs of accurate prediction of material deterioration under complex corrosion conditions of high-sulfur tailings anti-seepage cushion layer.
[0249] Additionally, it should be noted that, as an optional option, the liquid phase excitation component described in S3 contains a biomimetic modification solution, which is prepared by compounding pure water, PDADMAC, and PAAS, and is used to synergistically regulate the hydration reaction and micro-interface structure of the gelation system.
[0250] In the biomimetic modified solution, based on 100 parts of pure water, the amount of PDADMAC added is 14 parts and the amount of PAAS added is 6 parts; the dosage range of the biomimetic modified solution relative to the total mass of solid waste material is 3% to 16%.
[0251] The technical solution of the present invention will be verified and explained in detail and completely through the following experimental examples. The preparation process, testing method and modification effect of the modified cementitious material will be explained in combination with specific proportions and process parameters. However, the present invention is not limited to the following experimental examples.
[0252] Experimental raw materials and basic proportions: This experiment uses a total solid waste material mass of 150g as a fixed baseline, and a fixed main material proportion: 22.5g of calcium carbide slag and 127.5g of mineral powder; fixed composite salt activating components: 37.6g of water glass solid and 1.9g of NaOH solid, with the activator modulus kept constant at 1.5.
[0253] The biomimetic modification solution is prepared in strict accordance with the proportions specified in claim 3: 100 parts of pure water are used as a base, 14 parts of PDADMAC and 6 parts of PAAS are added, and the mixture is stirred until completely dissolved to prepare a uniform and stable biomimetic modification solution.
[0254] To verify the modification effect of different dosages of biomimetic solutions, a blank control group and a multi-gradient experimental group were set up. The water-cement ratio and mixing water volume were precisely matched for each group. The specific raw material ratio parameters are shown in Table 1 below.
[0255] Table 1: Raw material ratio parameters of modified cementitious materials with different biomimetic solution dosages.
[0256]
[0257] The above-mentioned biomimetic solution dosage ranges cover 3% to 16% of the total mass of solid waste main materials, which fully conforms to the preferred dosage range defined in claim 3. The experimental variables are singular and the gradient is reasonable, which can effectively verify the modification effect of the biomimetic solution.
[0258] Overall Experimental Process: S1. Raw Material Stepped Temperature-Controlled Dehydration and Lattice Consolidation Pretreatment: Calcium carbide slag and phosphogypsum raw materials were used separately. A stepped temperature-controlled dehydration process was employed, sequentially completing low-temperature equilibration, medium-temperature dehydration, and high-temperature desorption treatments. The temperature control parameters for each stage were adaptively adjusted according to the initial moisture content of the raw materials. The dehydrated dried powder was placed in an atmospheric pressure salt solution system for low-temperature gypsum crystal transformation treatment, while simultaneously performing in-situ lattice consolidation to fix unstable phosphorus and fluorine impurities in the matrix. During the experiment, the fluoride ion lattice distortion coefficient, the relative water vapor partial pressure of the cover soil, the trace organic matter crystal plane retardation coefficient, the critical activity of calcium ion supersaturation precipitation, and the metastable retention coefficient of the crystal phase during the drying stage were collected simultaneously to construct a complete raw material modification working condition dataset and complete the raw material pretreatment calibration. Meanwhile, mineral powder, water glass, and NaOH dry powder were pretreated using the same dehydration process to ensure homogeneous drying of the raw materials.
[0259] S2, Homogeneous Mixing of Dry Powder: The carbide slag, phosphogypsum powder and mineral powder after S1 pretreatment are mixed and blended in a dry manner according to the ratio of calcium, silicon, sulfur and aluminum elements. After thorough mixing, a homogeneous and stable composite powder raw material is obtained for subsequent activation and pulping.
[0260] S3. Stepwise activation and control of composite salts (including biomimetic solution modification): The composite salt activation component of this invention is composed of alkali metal silicates and basic salts, and is added in two steps: a dry powder solid phase and a liquid phase. In the final stage of S2 dry powder mixing, water glass and NaOH dry powder solid phases are uniformly incorporated into the composite powder, allowing them to fully adhere to the surface of the powder particles. After the dry powder system is homogeneous and stable, the corresponding biomimetic modification solutions of each group are pre-mixed with added pure water to prepare a homogeneous liquid phase system, which is then uniformly incorporated into the dry powder system to complete the stepwise sequential activation, thus obtaining fresh gel slurry corresponding to each group ratio.
[0261] S4. Staged pressure molding, curing, and in-situ hydration monitoring: Each group of fresh cementitious slurry was staged and pressure-molded in sequence according to the following time periods: low-pressure venting, medium-pressure shaping, and high-pressure compaction. The molding pressure and holding time of each stage were adapted to the parameter range of the seepage prevention working conditions. After molding, standard specimens were prepared according to the service scenario and matched with constant temperature curing or dry-wet alternating curing system. During the early hydration window of the slurry, continuous in-situ monitoring of hydration conductivity was carried out throughout the process. The surrounding rock geothermal drift correction coefficient, electrode passivation film growth rate, capillary water ion precipitation coefficient, and mineral dust ion adsorption coefficient were collected simultaneously. The monitoring baseline was dynamically corrected to eliminate interference from the closed environment and accurately collect the early hydration ion evolution parameters of each group of samples.
[0262] S5. Layered cutting and standard sample preparation: After the curing parameters of each group of specimens meet the standards, layered cutting is carried out along the uniform thickness direction of the specimens using a non-disturbance precision cutting process. According to the test requirements of impurity detection, microstructure detection, and interface mechanical testing, the cut specimens are divided into zones, classified, and sealed. All specimens are stored in a constant temperature and humidity sealed environment to ensure the accuracy and parallelism of subsequent multi-dimensional test data.
[0263] S6. Multi-stage continuous fractional extraction and detection: The samples of each component zone are sequentially extracted using a three-stage time-series extraction system of weak acid dissolution, medium salt dissolution, and strong complexation to progressively remove phosphorus and fluoride impurities in the free leakage state, surface complexation state, and lattice solidification state inside the gel matrix; the dissociation constant of the buffer solution and the equilibrium pH of the system are strictly controlled to meet the requirements of solid waste environmental protection testing standards; the entire extraction process is kept at a constant temperature and static, and the surface complexation equilibrium coefficient of phosphorus and fluoride ions is collected in real time to accurately quantify the differences in diffusion hindrance characteristics of impurities inside the matrix under different biomimetic solution dosages.
[0264] S7. Quantitative Analysis of Infrared Spectroscopy and Microscopic Detection of Nanoindentation: Before detection, according to the quantitative standard of silicate gel spectroscopy, the resolution threshold of CSH oligomer characteristic peaks was calibrated as the judgment criterion. Infrared spectral scanning was carried out on each group of samples to collect the half-width at half-maximum (WHM) shift of silicon-oxygen tetrahedron characteristic peaks and the baseline drift of hydroxyl peaks. By filtering out impurity peak interference and capillary scattering loss error through preset thresholds, the quantitative analysis of spectra was completed. Subsequently, single-point nanoindentation detection was carried out on the micron-contact transition zone of the sample gel-tailings. At the same time, the interface sulfur element segregation softening coefficient, local alkali dissolution modulus attenuation coefficient, stress concentration coefficient of ettringite needle crystal tip, unloading rebound deformation coefficient of pore region, and polishing surface damage thickness correction coefficient were collected to obtain the degree of polymerization of CSH gel and the micromechanical parameters of the interface, and the microscopic performance calibration of the sample was completed.
[0265] S8. Comprehensive Performance Testing and Evaluation: Integrating the measured working conditions, hydration parameters, phosphorus and fluorine impurity diffusion parameters, microstructure and interfacial mechanical parameters of each group of samples from S1 to S7, and based on the power-law calculation model of cumulative damage in the interfacial transition zone, a quantitative correlation between the degree of gel polymerization and the long-term strength of the material is constructed, and the quality testing and comprehensive performance evaluation of the cementitious materials under different biomimetic solution dosages are completed.
[0266] Comparison between the blank group D4-1 and the gradient dosage experimental group shows that within the biomimetic solution dosage range of 3% to 16%, the biomimetic modified solution can effectively synergistically regulate the hydration reaction of the cementitious system with the composite salt activating components, optimize the CSH gel polymerization degree, improve the microscopic defects in the transition zone of the cementitious-aggregate interface, inhibit sulfur segregation and alkali corrosion damage, and significantly improve the matrix density and the ability to inhibit the solidification of phosphorus and fluorine impurities. When the biomimetic solution dosage is in the optimal gradient range, the material interface damage accumulation rate is significantly reduced, and the mechanical properties and the stability of the seepage-proof solid waste are greatly improved, fully verifying the scientificity and practicality of the process system and biomimetic solution modification ratio of this invention.
[0267] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. For those skilled in the art, any alternative improvements or transformations made to the implementation of the present invention fall within the protection scope of the present invention.
[0268] Any aspects of this invention not described in detail are well-known to those skilled in the art.
Claims
1. A method for preparing and testing the quality of modified cementitious materials based on carbide slag and phosphogypsum, characterized in that, Includes the following steps: S1. Perform a stepped temperature-controlled dehydration process on carbide slag and phosphogypsum, then place them in a normal pressure salt solution system for low-temperature gypsum crystallization treatment, and simultaneously carry out in-situ lattice consolidation. Collect liquid phase ion activity, crystal phase metastable state survival parameters and various working condition characteristic parameters to construct a raw material modification working condition dataset and complete the preprocessing. S2. Based on the ratio of calcium, silicon, sulfur and aluminum elements, the pretreated carbide slag and phosphogypsum solid waste powder are mixed with slag substrate to obtain uniform composite powder raw material. S3. The added compound salt is decomposed and step-by-step activation and control are implemented to complete the layered feeding operation of dry powder pre-mixing and delayed mixing of water phase in sequence, so as to obtain a uniform and stable fresh gel slurry. S4. Prepare specimens by graded pressure molding and matching curing of fresh cementitious slurry, and conduct continuous in-situ monitoring of hydration conductivity and collect early hydration ion evolution parameters. S5. After curing, the specimens are cut into layers and multiple sets of parallel test samples are prepared in different areas. S6. Perform multi-stage continuous fractional extraction on parallel samples in the partition to detect the diffusion and occurrence of phosphorus and fluorine impurities in the gel matrix, and quantitatively determine the diffusion hindrance characteristics of impurities in different occurrence forms in the matrix. S7. Perform infrared spectral deconvolution quantitative analysis and regional single-point nanoindentation microscopic detection on the sample in sequence, and simultaneously collect CSH gel polymerization degree and interfacial micromechanical characteristic parameters to complete the comprehensive calibration of the sample. S8. Based on the measured working condition parameters, impurity diffusion parameters, microstructure parameters and interface mechanical parameters collected throughout the process, complete the overall quality testing and comprehensive performance evaluation of the cementitious material.
2. The method according to claim 1, characterized in that, The specific steps of S1 are as follows: The two types of solid waste raw materials, carbide slag and phosphogypsum, are placed into the temperature control equipment respectively. The step temperature control and water removal are completed through three stages of time gradient: low temperature equilibrium, medium temperature dehydration, and high temperature desorption. The temperature control parameters of each stage are adaptively matched according to the initial moisture content of the solid waste raw materials. After the stepwise dehydration is completed, the dried powder is placed in a constant temperature and low temperature salt solution system under normal pressure to carry out a low temperature crystallization reaction. After the crystal transformation is completed, a wet planetary co-grinding operation is started to achieve in-situ lattice consolidation of soluble phosphorus and fluorine impurities in a solid-liquid coupled grinding environment; Simultaneously collect fluoride ion lattice distortion coefficient, relative water vapor partial pressure of cover soil, trace organic matter crystal plane retardation coefficient, calcium ion supersaturation precipitation critical activity, and crystal phase metastable retention coefficient during drying stage. Input the raw material modification working condition dataset to provide input parameters for the correction formula of metastable existence time of hemihydrate gypsum, and complete the crystal phase stability calibration and dynamic correction. The crystal phase stability was determined using the following formula for correcting the metastable duration of hemihydrate gypsum: ; In the formula: The duration of the metastable state of the hemihydrate gypsum crystalline phase is 12,000 to 20,000 hours. The effective duration of low-temperature crystal transformation under normal pressure is 2–6 hours. The lattice distortion coefficient for fluoride ions ranges from 0.01 to 0.
10. The critical activity for calcium ion supersaturation precipitation ranges from 1.05 to 1.
20. The relative water vapor partial pressure under soil cover conditions is taken as 0.60 to 0.
90. The value is the crystal plane retardation coefficient of trace organic matter, ranging from 0.85 to 0.98; The value is the metastable retention coefficient of the crystal phase during the drying stage, ranging from 0.90 to 0.
99.
3. The method according to claim 1, characterized in that, After the S1 raw material pretreatment process is completed, the S2 dry powder homogenization and mixing process is then carried out. First, the molar ratio range of the four core elements calcium, silicon, sulfur and aluminum in the system was determined, and the mass ratio of the pretreated carbide slag, phosphogypsum powder and S95 slag substrate was strictly limited. Then all dry powder components are fed into the mixing equipment. First, a low-speed premixing method is used to achieve initial dispersion of the large component materials, and then the high-speed fine mixing mode is switched.
4. The method according to claim 1, characterized in that, The specific steps of S3 are as follows: the composite salt is separated into two groups of materials: dry powder solid phase and aqueous solution phase, and the mass separation ratio range of the two groups of materials is fixed; in the final stage of S2 dry powder mixing, the solid phase activating component is added so that the solid phase activator is uniformly attached to the surface of the solid waste powder. After the dry powder mixing system is homogeneous and stable, the pre-dissolved liquid phase activating component is uniformly added into the mixing system to complete the step-by-step time-sequence activation control and obtain fresh slurry.
5. The method according to claim 1, characterized in that, The specific steps of S4 are as follows: Fresh gel slurry is subjected to graded pressurization molding in the sequence of low-pressure venting, medium-pressure shaping, and high-pressure compaction. The molding pressure and holding time of each stage are matched with the parameter range corresponding to the seepage prevention working conditions. After molding, standard specimens are prepared by matching the constant temperature curing or dry-wet alternating curing system according to the material service scenario. During the early hydration curing window of the slurry, continuous in-situ monitoring of hydration conductivity is carried out throughout the process. At the same time, the surrounding rock geothermal drift correction coefficient, electrode passivation film growth rate, capillary water ion precipitation coefficient, and mineral dust ion adsorption coefficient are collected. The monitoring baseline is dynamically corrected in multiple dimensions to eliminate the influence of the underground closed environment on the detection data and obtain accurate early hydration ion evolution parameters. In the process of multi-dimensional dynamic correction of the monitoring baseline, the logarithmic correction formula for multiple interference factors of hydration conductivity is used to complete the data correction: ; In the formula: : Environmentally corrected hydration conductivity, ranging from 0.05 to 0.50 S / m; These are the original conductivity values collected in situ on-site; This is a correction factor for geothermal drift in the surrounding rock, with a value range of 1.0 × 10⁻⁶. -6 ~5.0×10 -6 s -1 ; The effective duration for early hydration monitoring is 1080–1920 s; This is the electrode passivation film growth rate coefficient, with a value ranging from 1.0 × 10⁻⁶. -4 ~5.0×10 -4 s⁻¹; The characteristic time constant for electrode passivation is 3600s. The ion precipitation coefficient of capillary water secretion ranges from 0.01 to 0.05; The adsorption coefficient of mineral dust ions ranges from 0.005 to 0.
02.
6. The method according to claim 1, characterized in that, The specific steps of S5 are as follows: along the uniform thickness direction of the molded specimen, layer cutting is carried out using a non-disturbance precision cutting process; after cutting, multiple sets of parallel standard samples are prepared, and they are classified and sealed according to the testing requirements of impurity detection, microstructure detection, and interface mechanical detection; all samples are stored in a constant temperature and humidity sealed environment to provide a qualified sample carrier for subsequent graded extraction and micro-characterization processes.
7. The method according to claim 1, characterized in that, The specific steps of S6 are as follows: a three-stage sequential extraction system of weak acid dissolution, medium salt dissolution, and strong complexation is used to progressively remove phosphorus and fluoride impurities in the free leakage state, surface complexation state, and lattice solidification state inside the gel matrix; the dissociation constant of the buffer solution and the equilibrium pH of the system in each extraction system strictly follow the solid waste environmental protection testing standard range; the entire extraction process is kept at a constant temperature and static, and the surface complexation equilibrium coefficient of phosphorus and fluoride ions is collected in real time to define the diffusion hindrance characteristics of impurities in different forms.
8. The method according to claim 1, characterized in that, The specific steps of S7 are as follows: First, the CSH oligomer characteristic peak splitting threshold is pre-calibrated according to the silicate gel spectroscopy quantitative standard, which serves as the criterion for spectral data splitting; then, infrared spectroscopy scanning is performed on the sample, and the half-width at half-maximum (FWHM) shift of the silicon-oxygen tetrahedron characteristic peak and the baseline drift of the hydroxyl peak are collected simultaneously. The interference of floating dust peaks and the detection error caused by capillary scattering loss are filtered out by the preset threshold to complete the quantitative analysis of infrared spectral deconvolution; then, the sample is subjected to regional single-point nanoindentation microscopic detection to collect the degree of polymerization of CSH gel and the microscopic mechanical parameters of the interface, thus completing the comprehensive performance calibration of the sample. Based on measured parameters, a power-law calculation model for cumulative damage in the interface transition zone was constructed, and a quantitative correlation between the degree of gel polymerization and the long-term strength of the material was established to complete the material quality testing and performance evaluation.
9. The method according to claim 1, characterized in that, After the infrared spectroscopy analysis process is completed, the micron-level contact transition zone between the gelation and tailings of the sample is subjected to zoned single-point nanoindentation detection: During the testing process, the following parameters were collected simultaneously: the interface sulfur segregation softening coefficient, the local alkali dissolution modulus attenuation coefficient, the stress concentration coefficient at the tip of ettringite needle crystals, the unloading rebound deformation coefficient of the pore region, and the damage thickness correction coefficient of the polished surface. A damage accumulation model for the interface transition zone was constructed, and the degree of material damage accumulated slowly was calculated through the model. The calculation formula for the damage accumulation model in the interface transition zone is as follows: ; In the formula: The equivalent degradation modulus of the seepage prevention interface is taken in the range of 5–15 GPa. The intrinsic micro-elastic modulus of the cementitious matrix, with a value ranging from 10 to 20 GPa; The interfacial sulfur segregation softening coefficient ranges from 0.05 to 0.
20. The value range of the alkali dissolution modulus attenuation coefficient in the micro-region is 0.10 to 0.30; is the stress concentration factor at the tip of ettringite needle crystals, with a value ranging from 1.2 to 1.8; The unloading rebound deformation coefficient in the porous region ranges from 0.03 to 0.
10. This is the correction factor for the thickness of the polished surface damage, with a value ranging from 0.95 to 0.99.